The Need for Accessible Health Education - Laughlin, Michael K.; Benes, Sarah; Sherlock-Shangraw, Rebecca (Journal of Physical Education, Recreation and Dance, 2026)
Health education in preschool through 12th grade is an essential component of a well-rounded education and can positively impact student health and well-being. All school-age students deserve access to high-quality, effective health education. However, students with disabilities may not be receiving the health education they are entitled to for many reasons, including that there is not a clearly defined understanding of health education for students with disabilities. Working from the perspective that health education is both a social justice imperative and an important component of students’ “well-rounded education” under the Every Student Succeeds Act of 2015, this article is a call to action and brings attention to this area of need. It is framed around three critical questions: (1) Why do students with disabilities deserve access to health education? (2) How should health education for students with disabilities be conceptualized? (3) Where does accessible health education go from here? By articulating these questions and providing initial thoughts to spur further discussion and action, this article encourages invested partners and collaborators to address this critical need so that students with disabilities can meaningfully access the same high-quality health education opportunities as their peers. © 2026 SHAPE America.
Keywords: dept.hms

Testing Multiple Delivery Methods of the Virtual Exercise Games for Youth with T1D Peer Intervention: Protocol Development and Feasibility - Ash, Garrett I.; Nam, Soohyun; Mak, Selene S.; Stults-Kolehmainen, Matthew; Haughton, Adrian D.; Turek, Carolyn; Baker, Julien S.; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth G.; et al. (Hormone Research in Paediatrics, 2026)
Abstract – Introduction: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. Methods: The program included 6 versions: study 1 (1.1–1.4) included an active video game, and study 2 (2.1–2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. Results: Seventeen adolescents (median age 15.4 [IQR 14.6–16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%–11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min–90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = −1.12, 90% CI: [−1.78, −0.48]). Conclusions: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention’s impact on engagement with physical activity, glycemic outcomes, and quality of life. © 2026 S. Karger AG, Basel
Keywords: Diabetes; Peer support; Physical activity; Type 1; Video games; dept.hms

Introducing “Preservice Pipeline”—Why This Column, Why Now - Knipe, Bob (Journal of Physical Education, Recreation and Dance, 2026)
Future professionals learn to lead through a variety of professional opportunities, and it is time that JOPERD provides a forum dedicated to their development and an opportunity for them to lead as authors and coauthors. This article describes the new Preservice Pipeline column and how to submit articles. © 2026 SHAPE America.
Keywords: dept.hms

Testing multiple delivery methods of the virtual exercise games for youth with T1D peer intervention: protocol development and feasibility - Ash, Garrett; Nam, Soohyun; Mak, Selene; Stults-Kolehmainen, Matthew; Haughton, Adrian; Turek, Carolyn; Baker, Julien; Hieftje, Kimberly; Marks, Asher; Chmielewski, Annette; Shelver, Michael; Considine, Elizabeth; et al. (Hormone Research in Paediatrics, 2026)
INTRODUCTION: Adolescents with type 1 diabetes (T1D) face barriers to moderate-to-vigorous physical activity (MVPA) such as uncertainty with self-management, limited access to supportive environments, and stigma related to living with diabetes. Opportunities for peer activities with T1D role model support are limited. To address this need, we tested iterative refinements of pilot Virtual Exercise Games for Youth with T1D (ExerT1D) for feasibility and acceptability. METHODS: The program included 6 versions: study 1 (1.1-1.4) included an active video game, and study 2 (2.1-2.2) included a virtual reality (VR) active video game. All versions included T1D exercise management education by clinicians and goal-setting guided by young adult coaches with T1D. RESULTS: Seventeen adolescents (median age 15.4 [IQR 14.6-16.4] years, 7 non-Hispanic white, 8 male, median HbA1c 8.1% [IQR 7.4%-11.1%]) were enrolled. Participants rated the program, comfort, clinicians, coaches, and group cohesion high/very high. Motivation for the video game was high. Building T1D and MVPA self-management skills was rated excellent at most sessions, as were peer interactions and enriched communication after adding immersive VR in study 2. Transitions between VR apps caused delays of 19 ± 6 min per 60 min-90 min session. Compared to baseline, HbA1c or glucose management indicator decreased over time in an exploratory analysis (d = -1.12, 90% CI: [-1.78, -0.48]). CONCLUSIONS: In a small cohort, the ExerT1D program facilitated a supportive environment for engaging diverse youth with T1D in an MVPA program led by T1D coaches. Larger studies are needed to assess the intervention's impact on engagement with physical activity, glycemic outcomes, and quality of life.
Keywords: Glycemic; Physical activity; Program evaluation; Protocol (science); Quality (philosophy); Quality of life (healthcare); dept.hms

The effect of high dose creatine supplementation on thermoregulatory adaptation during a standard heat acclimation protocol - Martin, David; Thornton, Staci; Langan, Seam; Navarro, John; Brewer, Gabrielle; Szymanski, Michael; Huggins, Robert; Lunn, William; Rodriguez, Nancy; Casa, Douglas; Lee, Elaine (Medicine & Science in Sports & Exercise, 2025)
Keywords: Acclimatization; Analysis of variance; Core temperature; Creatine; Dehydration; Heat stress; Rectal temperature; Thermoregulation; dept.hms

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

National Trends in Athletic Training Service Provision in U.S. High Schools: A Five-Year Longitudinal Assessment - Kim, D; Eason, Christianne; Grubb, Joseph; Casa, Douglas; Coleman, Kelly; Filep, Erica; Huggins, Robert (Current Sports Medicine Reports, 2026)
Keywords: Athletes; Athletic training; Sports medicine; Trainer; Training (meteorology); dept.hms

Comparison Of Measures Of Arterial Stiffness Between Women With And Without Polycystic Ovarian Syndrome - Lecher, Madison; Rupp, Kristie; Latchman, Peter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Arterial stiffness; Blood pressure; Body mass index; Etiology; Polycystic ovary; Pulse wave velocity; dept.hms

Similar Relative Energy Deficiency In Sport (REDs) Variables In Men And Women NCAA Distance Runners - Bryan, J.; Rupp, Kristie; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Basal metabolic rate; Bone mineral; Doubly labeled water; Dual energy; Energy expenditure; Energy metabolism; Fat free mass; Fat mass; Physical activity; dept.hms

Assessing Asymmetry In Collegiate Sprint And Intermediate Hurdlers - Gregory, Robert; Dale, Hunter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Asymmetry; Ground reaction force; Impulse (physics); Jump; Plyometrics; Sprint; dept.hms

Effect Of Creatine Monohydrate Supplementation On VO2 Kinetics In Aerobically Fit Adults - Raymond, Emerson; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Blood lactate; Creatine; Crossover study; Heart rate; Lactate threshold; Percentile; Treadmill; VO2 max; Ventilatory threshold; dept.hms

Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

936 - Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: dept.hms

Forgotten Learners: High School Transition Students With Disabilities - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2026)
Because physical literacy and activity are not emphasized in special education as they are in physical education or adapted physical education (PE/APE), this editorial explores two important questions: Do high school transition students receive PE/APE programming? And are PE/APE teachers introduced or exposed to transition services at any point in their teacher training?. © 2026 SHAPE America.
Keywords: dept.hms

Reply - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
Keywords: dept.hms

Remote Lesson Study as Continuing Professional Development for Physical Education Teachers - Colburn, Jeffrey; Knipe, Robert; Doherty, Brooke; Stephenson, Rachyl; Hamilton, Xiaofen (Journal of Teaching in Physical Education, 2026)
Purpose: This study investigated experiences of physical education teachers (PETs) participating in online remote andragogy-based lesson study (AbLS) during a pandemic. Method: Five PETs participated in this phenomenological case study. Seventeen online AbLS collaborative meetings took place via Zoom software. Three rounds of semistructured interviews were conducted and analyzed using collaborative qualitative analysis. Results: Three themes emerged: (a) AbLS facilitated depth of learning, increasing professional and individual growth; (b) AbLS structure influenced experience; and (c) the professional community of AbLS supported a natural adult learning (andragogical) environment. Discussion/Conclusion: Remote AbLS presented benefits for these PETs beyond professional learning that prior continuing professional development had not, including a sense of community, belonging, and professional worth. AbLS may have implications for research in perceived mattering and continuing professional development facilitation for PETs. Remote AbLS may bolster PETs in challenging local learning communities. © 2026 Human Kinetics, Inc.
Keywords: andragogy; dept.hms; marginalization; professional learning; remote communities

Healthy Futures for Young Women With Obesity: A Mixed Methods Study - Rupp, Kristie; Bryan, JohnM.; Abel-Berei, Catherine (American Journal of Health Promotion, 2025)
Keywords: Focus group; Health promotion; Intervention (counseling); Mental health; Obesity; Perception; Physical activity; Psychological intervention; Psychosocial; dept.hms; health behavior; weight bias; weight stigma; women’s health

Availability of School-Based Sexual and Reproductive Health Services - Zhong, Anthony; Szlosek, Donald; Gao, Chloe; Dang, Nhu; Benes, Sarah (American Journal of Preventive Medicine, 2025)
Keywords: Health services; MEDLINE; Public health; Reproductive health; Sexual behavior; dept.hms

Athletic Training Services Trends Between Public and Private High Schools: A 5-Year Retrospective Analysis - Kim, Donghyeon; Defino, Amir; Eason, Christianne; Casa, Douglas; Yoo, Chaeyeon; Yoshihara, Ayami; Coleman, Kelly; Filep, Erica; Huggins, Robert (Journal of Athletic Training, 2025)
Context Access to athletic trainers (ATs) in high schools is crucial for student-athlete (SA) safety. Although most high schools in the United States have access to athletic training services (ATS), no authors have longitudinally compared ATS trends between public (PUB) and private (PVT) school sectors. Objective To compare ATS trends between PUB and PVT schools from the 2018–2019 through 2022–2023 academic years. Design Longitudinal cross-sectional study. Setting Online survey. Main Outcome Measure(s) High school responses to the Athletic Training Locations and Services survey from all 50 US states and the District of Columbia were queried from the 2018–2019 to 2022–2023 academic years. Average numbers of SAs ( SAs ), sports ( Sports ), full-time ATs ( FtATs ), part-time ATs ( PtATs ), and the sum of full-time and part-time ATs ( ATs ), along with the average weekly contracted hours ( CHrs ) and actual hours ( AHrs ) per school, and ratios of SAs : ATs , Sports : ATs , CHrs : SAs , CHrs : Sports , AHrs : SAs , and AHrs : Sports were examined to track ATS trends over 5 years and compare PUB vs PVT schools. Results Public schools had higher SAs and Sports vs PVT schools (both P < .001). Private schools had higher ATs , CHrs , and AHrs than PUB schools (all P < .050). Ratios of SAs : ATs and Sports : ATs were higher in PUB schools, whereas CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports were higher in PVT schools (all P < .050). From 2018–2019 to 2022–2023, PUB schools increased Sports and Sports : ATs ; PVT schools increased SAs , Sports , ATs , and SAs : ATs (all P < .050). Over the years, PUB schools decreased CHrs : Sports and AHrs : Sports ; PVT decreased CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports . FtATs increased in both sectors, whereas PtATs decreased in only PVT schools. Conclusions Overall, ATS were more extensively provided in PVT schools, based on ATs and ATS hours. Both sectors increased FtATs , which is encouraging. However, as SAs and Sports increased, ATS provided per SA and sport declined.
Keywords: Athletes; Athletic training; Context (archaeology); MEDLINE; Private sector; Training (meteorology); athletes; dept.hms; safety; sports; student health services

Educational Programming to Prevent Violence in Schools in the United States: An Analysis of School Health Profiles - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
This repeated, cross-sectional study examined trends in the availability of school-based programming to prevent violence in middle and high schools across the United States from 2008 to 2020. Overall, violence prevention programming increased in respondent schools throughout the study period. However, important gaps remain, with lingering state-level disparities.
Keywords: Human factors and ergonomics; Injury prevention; Occupational safety and health; Poison control; Respondent; Suicide prevention; adolescent health; dept.hms; health education; school violence prevention; teacher training; youth violence prevention

Position Statements for Advocacy: Does Using Physical Activity as Punishment Make Students Leave Physical Education Wanting to Hide or Seek? - Paulson, Lisa; Knipe, Robert (Strategies, 2025)
This article explains how to use and apply the SHAPE America position statement “Physical Activity Should Not Be Used as Punishment and/or Behavior Management” in one’s own teaching and as an advocacy tool. © 2025 SHAPE America.
Keywords: dept.hms

Adolescent Concern for Body Weight and Engagement in Unhealthy Weight Control Behaviors - McCoy, Stephanie; Bryan, Jessica; Rupp, Kristie (American Journal of Health Promotion, 2025)
Keywords: Binge eating; Body mass index; Body weight; Clinical psychology; Demography; Disordered eating; Eating disorders; Environmental health; Gerontology; Internal medicine; Logistic regression; Medicine; Obesity; Odds; Odds ratio; Pill; dept.hms; eating behaviors; obesity; psychosocial health

Is Your Physical Education Adapted or Adaptive? - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2025)
For decades, adapted physical education advocates have passionately engaged in a debate over two adjectives: adapted vs. adaptive. This article explores the reasons why one is preferred over the other and why it matters, especially to students with disabilities. © 2025 SHAPE America.
Keywords: dept.hms

An Exergames Program for Adolescents With Type 1 Diabetes: Qualitative Study of Acceptability - Mak, Selene S.; Nally, Laura M.; Montoya, Juanita; Marrero, Rebecca; DeJonckheere, Melissa; Joiner, Kevin L.; Nam, Soohyun; Ash, Garrett I. (JMIR Diabetes, 2025)
Background: Numerous barriers to moderate to vigorous physical activity exist for youths with type 1 diabetes (T1D). The virtual exercise games for youth with T1D (ExerT1D) intervention implement synchronous support of moderate to vigorous physical activity including T1D peers and role models. Objective: This study aims to understand the acceptability of this intervention to participants. Methods: We conducted postprogram, semistructured, televideo interviews with participating youths to elicit perspectives on the acceptability of the intervention and experience with the program. Two coders independently reviewed and analyzed each transcript using a coding scheme developed inductively by senior researchers. Discrepancies were resolved by team discussion, and multiple codes were grouped together to produce 4 main thematic areas. Results: All 15 participants provided interviews (aged 14-19 years; 2 nonbinary, 6 females; median hemoglobin A1c level of 7.8% (IQR 7.4%-11.2%), 5 with a hemoglobin A1c level of ≥10%). Qualitative data revealed four themes: (1) motivation to engage in physical activity (PA)—improving their physical capabilities and stabilizing glucose levels were cited as motivation for PA and challenges of living with T1D were cited as PA barriers; (2) experience with and motivation to manage diabetes while engaging in PA—participants provided details of accommodating the inherent uncertainty or limitations of PA with diabetes and sometimes preparing for PA involved psychological and motivational adjustments while some relayed feelings of avoidance; (3) peer support encouraged engagement with the intervention—participants appreciated the peer aspects of components of ExerT1D and participants’ reflections of the facilitated group experience highlight many benefits of a small-group virtual program; and (4) improvements in PA and diabetes self-management efficacy—all participants credited the program with improving or at least raising awareness of T1D management skills. Conclusions: Our virtual PA intervention using an active video game and discussion component provided adolescents with T1D the confidence and peer support to engage in PA, improved awareness of diabetes-specific tasks to prepare for exercise, and improved understanding of the effect of PA on glucose levels. Engaging youths with a virtual video game intervention is a viable approach to overcome barriers to PA for adolescents with T1D. Trial Registration: ClinicalTrials.gov NCT05163912; https://clinicaltrials.gov/ct2/show/NCT05163912
Keywords: Computer science; Diabetes mellitus; Medicine; Preprint; Psychology; Qualitative research; Sociology; Type 2 diabetes; World Wide Web; dept.hms; peer-reviewed

Integrating edTPA into Physical Education Teacher Education: Teacher Educators’ Perceptions and Experiences in Preparing Teacher Candidates - Olsen, Edward B.; Wyant, James D.; Tsuda, Emi; Laughlin, Michael K.; Baxter, Deborah S. (Journal of Teaching in Physical Education, 2024)
Purpose: In the United States, 15 states maintain policies and 25 states represent some level of edTPA affiliation. This study investigated how the edTPA was integrated and aligned into different physical education teacher education (PETE) programs in New Jersey. It also sought to understand teacher educators’ perceptions and experiences in preparing teacher candidates for the edTPA. Methods: This study utilized three data sources: semistructured interviews (n = 4), one focus group interview (n = 1), and documents (n = 17). Data analysis reflected a conventional approach toward qualitative content analysis. Results: In analyzing the data, four themes were established: (a) benefits and drawbacks of edTPA in PETE, (b) goals and success of edTPA in PETE, (c) integrating edTPA into PETE—macro- and microperspectives, and (d) analytic insights into edTPA and future recommendations. Discussion/Conclusion: In states requiring the edTPA, early exposure, scaffolding, curriculum mapping, and a shared mission and vision are critical. In states not requiring the edTPA, programs may want to consider indicators of performance, such as artifacts, reports, elements of the edTPA, university-based assessments, or a portfolio. Regardless of the type of assessment, “a” performance-based assessment may help to determine teacher candidates’ ability to plan, instruct, assess, and reflect.
Keywords: dept.hms; faculty; peer-reviewed; performance-based assessments; preservice teachers

Response to a standard behavioral weight loss intervention by age of onset of obesity - Rupp, K.; Taverno Ross, S. E.; Lang, W.; Jakicic, J. M. (Obesity Science & Practice, 2016)
Background The purpose of this study was to examine weight loss, physical activity, fitness and diet changes in response to a standard behavioral weight loss intervention in adults with self-reported juvenile onset (n = 61) or adult onset (n = 116) obesity. Methods Participants (n = 177; 43.0 ± 8.6 years; body mass index [BMI] = 33.0 ± 3.4 kg m−2) engaged in an 18-month standard behavioral weight loss intervention. Participants were randomized into three different intervention groups as part of the larger parent trial. BMI, physical activity, fitness and diet were assessed at baseline, 6, 12 and 18 months. Separate adjusted mixed models were constructed using SAS version 9.4 (SAS Institute, Cary, NC). Results There was significant weight loss, increased physical activity, improved fitness and reduced caloric intake over time (p < 0.001). There were no significant differences in these outcome variables by obesity onset group. However, there was a significant group by time interaction for fitness (p = 0.001), with the adult onset making significantly greater gains in fitness from baseline to 6 months (p < 0.001); however, this difference was no longer present at 12 or 18 months. Conclusions With the exception of fitness at 6 months, weight loss, physical activity and diet did not differ between juvenile onset and adult onset participants, suggesting that those with juvenile onset obesity are equally responsive to a standard behavioral weight loss intervention in adulthood.
Keywords: Obesity; dept.hms; physical activity; weight loss interventions

What’s Going on Out There? An exploration of K–12 PE Curricular Models and Content Taught in Public Schools - Hodges, Michael; Laughlin, Michael; Brusseau, Timothy (The Physical Educator, 2018)
Little is known about which curricular models and activity units are being taught in public schools. This exploratory study examined the K–12 physical education (PE) content and curricular models being implemented. Supervisors of PE recruited from one northeastern state participated in a 25-item questionnaire. Descriptive statistics and frequencies were calculated. Sixty-nine of 92 questionnaires were usable and included in the data analysis. Findings suggest that few districts were using a curricular model at the elementary (K–5) level (27%). Another common response of adopted curricular models at the elementary level was Movement Education (17.6%). At the secondary level, No Model (35%) and Fitness Education (25.6%) were common responses. Specific units such as volleyball, basketball, and weight training yielded the highest responses, while field hockey, golf, archery, lacrosse, and tennis yielded the fewest responses. The findings suggest that K–12 PE curricula may not reflect current trends and mandates. The key determinants could be a lack of curricular model use and heavy reliance upon activities known to present challenges toward standards-based education (i.e., softball). Perhaps K–12 PE and PE preparation programs can connect to effectively articulate a curriculum, and adopt and train on curricular approaches aiming to increase teacher effectiveness and reach national standards.Subscribe to TPE
Keywords: Content; Curricular Models; PETE; Units; dept.hms

Development of a Scale Measuring Chinese Preservice Physical Education Teachers’ Beliefs About the Physical Education Profession - Fan, Yao; Keating, Xiaofen D.; Liu, Jingwen; Zhou, Ke; Shangguan, Rulan; Knipe, Robert (The Asia-Pacific Education Researcher, 2018)
This project aimed to develop a valid and reliable scale measuring Chinese preservice physical education teachers’ beliefs about the physical education profession (PPET-BPEP). The domains and items were created from a conceptual analysis of the previous literature and PPETs’ responses to an open-ended survey. Six experts in the field of physical education and educational psychology evaluated the content validity of the scale. The reliability and factorial validity of the scale were examined utilizing a sample of 696 Chinese PPETs. The PPET-BPEP scale with 12 items embedded in two domains revealed acceptable content validity, internal structure validity, and internal consistency. The two domains were labeled as “sense of calling” and “value of physical education profession” based on the shared content of items in each domain. We recommend using PPET-BPEP scale for PPET recruitment and preparation. The scale can also help establish teacher belief scales in other subject matters. Future validation of the scale is needed in different countries and institutions.
Keywords: Future physical education teacher; Professional beliefs; Survey development; Validity and reliability; dept.hms

Acute arterial stiffness responses to on-ball kneeling and sitting: Effects of exercise fragmentation and exercise order - Xiao, Yaru; Chen, Wei; Latchman, Peter; Zhou, Zhixiong; Zhu, Weili (European Journal of Applied Physiology, 2025)
Keywords: Arterial stiffness; Ball balance; Blood pressure; Cardio-ankle vascular index; Cardiology; Exercise physiology; Fragmentation; Human physiology; Internal medicine; Kneeling; Medicine; Moderate exercise; Order; Physical exercise; Physical medicine and rehabilitation; Physical therapy; Posture; Sitting; Sports medicine; dept.hms; peer-reviewed

Sex Differences in Response to a 12-Week Resistance Training Exercise Intervention After Cardiac Surgery: A Proof-of-Concept Intervention Trial - Safdar, Basmah; Jarman, Angela; Madsen, Tracy; DeLamielleure, Lauren; Zhou, Bin; Axtell, Robert; Geirsson, Arnar; Mangi, Abeel (Clinical Therapeutics, 2025)
Keywords: Cardiac rehabilitation (CR); Cardiac surgery; Cardiovascular disease (CVD); Intervention (counseling); Medicine; Nursing; Physical therapy; Randomized controlled trial; Resistance strength training; Resistance training; Safety and feasibility; Sex differences; Surgery; dept.hms; peer-reviewed

Leadership: Athletes and Coaches in Sport - Academy, U. S. Sports (The Sport Journal, 2016)
Authors: Dr. Sharon P. Misasi*, Dr. Gary Morin and Lauren Kwasnowski Dr. Sharon P. Misasi is a Professor of Exercise Science at Southern Connecticut State University. Dr. Gary Morin is a Professor of Exercise Science, Assistant Athletic Trainer and Program Director of the Athletic Training Education Program. Lauren Kwasnowski is a Research assistant for this
Keywords: dept.hms

The relationship between heart rate variability and recovery heart rate in women - Latchman, P.; Gates, G.; Axtell, R.; Lunn, W.; Stachenfeld, N.; Meersman, R. De (Autonomic Neuroscience: Basic and Clinical, 2015)
Keywords: dept.hms

Dyspnea - Kreiger, J.; Niekrash, C.; Fitzgerald, C. (The Encyclopedia of Elder Care: The Comprehensive Resource on Geriatric Health and Social Care, 2017)
Praise for the Third Edition:“The third edition of this outstanding resource reflects the many advances in the care of older people that have occurred since the publication of the second edition…The vast bulk of the content is accessible and relevant to an international audience. The indexing and cross-referencing are excellent... Score: 5/5 stars."-- Margaret Arthur, Nursing Standard"The information [in this book] is amazing. I reviewed topics in which I have expertise and was very satisfied. This is an excellent addition to my library and I will refer to it often, much like a medical dictionary... Score: 90, 4 Stars."--Doody's Medical Reviews“Provides 273 comprehensive, yet succinct, entries on a variety of topics related to elder care. In addition, many of the entries include see also references that help readers easily navigate the book. Recommended."--Choice: Current Reviews for Academic LibrariesThis expanded, one-of-a-kind reference of more than 250 entries provides a comprehensive guide to all of the essential elements of elder care across a breadth of health and social service disciplines. Responding to the needs of providers, directcare workers, family, and other caregivers, the diverse array of entries included in this encyclopedia recognize and address the complex medical, social, and psychological problems associated with geriatric care. In addition to a brief, accessible summary of each topic, entries include several key references, including web links and mobile apps for additional sources of information.This updated edition contains more than 30 new entries written by renowned experts that address a variety of elder care topics.New to the Fourth Edition:New entries addressing Ethics Consultation, Eye Disorders, Pain – Acute and Chronic, and many othersKey Features:Provides succinct descriptions of over 250 key topics for health and social service cliniciansOffers crucial information for elder care providers across all settings and disciplinesDistills current, evidence-based literature sourcesWritten by nationally recognized expert researchers and cliniciansIncludes links to useful websites and mobile apps
Keywords: dept.hms

Cognitive Performance Does not Limit Physical Activity Participation in the Lifestyle Interventions and Independence for Elders Pilot Study (LIFE-P) - Reid, K. F.; Walkup, M. P.; Katula, J. A.; Sink, K. M.; Anton, S.; Axtell, R.; Kerwin, D. R.; King, A. C.; Kramer, A. F.; Miller, M. E.; Myers, V.; Rosano, C.; et al. (The journal of prevention of Alzheimer's disease, 2017)
We examined whether multiple domains of baseline cognitive performance were associated with prospective physical activity (PA) adherence in the Lifestyle Interventions and Independence for Elders Pilot study (LIFE-P). The LIFE-P study was a ...
Keywords: dept.hms

Fostering cultural competence: Exploring client perception in a health coaching intervention among college students - Oh, Seungbin; Benes, Sarah; Yan, Zi (Nursing & Health Sciences, 2024)
Health coaching could be an innovative approach to develop student coaches' cultural competence (CC) among future health professionals. The current mix-method study design explored the impact of an 8-week peer health coaching intervention among college students on CC, from both student health coaches (i.e., students majored in health sciences who completed health coaching training and acted as health coach) and student clients' perspective. Nine student coaches and 24 student clients participated in the study. The quantitative analysis showed an increase in the clients' perceived level of coaches' CC between the pre- and posttest. The qualitative analysis revealed three themes, including varying levels of awareness, respectful and culturally responsive coaching, and cultural connection. Implications and recommendations for educators and researchers are discussed.
Keywords: cultural competence; cultural humility; dept.hms; health coaching; mixed-method design; peer-reviewed

Rethinking Education from Patients' Perspectives - Harrison, Jill; Frampton, Susan; McNeal, Gloria J.; Todorova, Elena; Wahl, Carol; Kreiger, Joan (ABNF Journal, 2019)
Person-centered care (PCC) is a term used to describe an individualized approach to patient care that engages patients and families as partners in meaningful ways to create a comprehensive, collaborative, and customized plan and experience of care. Although some healthcare fields of study, such as the Quality and Safety Education for Nurses (QSEN) model, have adopted and integrated person-centered care concepts and competencies into their curricula, there remains a critical gap in higher education to systematically integrate person-centered care into the curricula and assessment of interprofessional healthcare fields of study. While the delivery of person-centered care by healthcare professionals requires education and training in PCC concepts, this training has primarily occurred on the job, without a standardized and comprehensive curriculum to systematically teach and assess PCC competencies to students in interprofessional healthcare and medical degree programs. Until recently, the educational foundations for healthcare disciplines were drawn primarily from biomedical, business, and nursing models, not from patients' points of view. In this article, we consider why teaching and evaluating PCC concepts should be the foundation of all interprofessional health education. We first review the perspectives of relevance to our argument and then advocate for a person-centered paradigm shift for interprofessional healthcare and medical education and training. Next, we argue that integrating and evaluating students' understanding and application of PCC concepts in all healthcarerelated disciplines will ensure that graduates receive the most current and relevant preparation for careers in healthcare and that this aligns with the expectations of patients as consumers.
Keywords: Curriculum; Education; Evaluation; GenderWatch; Interprofessional education; Patient; Person-centered care; Teaching method; Y; dept.hms; peer-reviewed; ⛔ No DOI found

State Physical Education Policy Changes From 2001 to 2016 - Dauenhauer, Brian; Keating, Xiaofen; Stoepker, Peter; Knipe, Robert (Journal of School Health, 2019)
ABSTRACT BACKGROUND State policies influence the quantity and quality of educational programs delivered in schools. This study examined state physical education policy changes from 2001 to 2016 by analyzing data reported in The Shape of the Nation Report . METHODS Policies related to state mandates for physical education, time/credit requirements, assessment and fitness testing requirements, adoption of state standards, and allowance of substitutions were analyzed over 5 editions of the report using repeated measures statistics. RESULTS A majority of state physical education‐related policies have not changed over the past 15 years despite calls by numerous public health agencies for enhanced physical education in schools. There was, however, a significant increase in the number of states adopting teaching standards and requiring assessment and fitness testing in physical education, mirroring a broader shift in education toward standards, assessment, and accountability. CONCLUSIONS Despite improved rigor in physical education through the adoption of standards and assessment practices, physical education continues to be marginalized in schools by a lack of curricular time and inappropriate substitution policies. Stronger policies are needed for physical education to have a substantial impact on school health.
Keywords: dept.hms; peer-reviewed

Exercise Prescription - Older Adults - Axtell, Robert; Robertson, M. I. (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Muscular Strength Assessment - Axtell, Robert (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Spinal cord injury management policies in high school sports as reported by athletic administrators - Scarneo-Miller, Samantha E.; Swartz, Erik E.; Register-Mihalik, Johna K.; Coleman, Kelly A.; Emrich, Christina M.; DiStefano, Lindsay J. (Translational Journal of the American College of Sports Medicine, 2024)
Introduction/Purpose Athletic administrators (AA) in U.S. high schools are uniquely positioned to provide guidance and endorsement for the prevention and management of common sport-related catastrophic injuries, such as the development of a spinal cord injury management (SCIM) policy. The purpose of this project was to evaluate AA’s knowledge of comprehensive SCIM policies in U.S. high schools. Secondarily, we aimed to investigate the factors, facilitators, and barriers to the development and adoption of comprehensive policies. Methods An online questionnaire was distributed to 6423 AA working in U.S.-based high school athletics, with 366 included in the final data analysis. The questionnaire evaluated AA’s knowledge of comprehensive SCIM policies addressing components of adoption, documentation, and communication. The questionnaire was developed based on the 2002 “National Athletic Trainers’ Association Position Statement: Acute Management of the Cervical Spine-Injured Athlete.” The questionnaire also inquired about facilitators and barriers to developing and adopting comprehensive policies. Proportions were calculated for policy adoption, and independent-samples t-tests evaluated the influence of athletic training services on comprehensive SCIM policies. Results About half of AA (49.2%, n = 180/366) reported having all recommended components of a written SCIM policy. AA who had access to an athletic trainer (yes = 62.9%, no = 18.1%, unknown = 19%) were more likely to have a comprehensive SCIM policy compared with those without access (80.6% vs 19.4%, χ21 = 7.091, P = 0.008, prevalence ratio = 1.24, 95% confidence interval = 1.03–1.50). The most commonly reported facilitator (49.9%) was “having a medical professional at the school,” and the main barrier (30.2%) was “my school would need more information, resources, assistance, etc.” Conclusions The findings identify areas for improvement in supporting the health and safety of children in high school participating in interscholastic athletics. Future dissemination and implementation research should develop strategies tailored to individual school community and need to improve SCIM policy adoption and implementation.
Keywords: dept.hms

The impact of an 8-week wellness peer coaching program on physical activity among college students: 1338 - Peacock, Jessica; Yan, Zi; Bowling, April; Benes, Sarah (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Marathon and ultra-endurance performance - Lunn, William R. (Medicine & Science in Sports & Exercise, 2023)
Keywords: dept.hms; peer-reviewed

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Prevalence of physical activity, sleep, and screen-time in youth before and during the covid-19 pandemic: 1735 - Rupp, Kristie; Friel, Ciaran P. (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Evaluating the Usability of the Wellness School Assessment Tool Whole School, Whole Community, Whole Child (WellSAT WSCC): A School Wellness Policy Assessment Tool - Connolly, K.; Koslouski, J.B.; Chafouleas, S.M.; Schwartz, M.B.; Edmondson, B.; Briesch, A.M. (Journal of School Health, 2023)
BACKGROUND: Adoption of the Whole School, Whole Community, Whole Child (WSCC) model has been slowed by a lack of available tools to support implementation. The Wellness School Assessment Tool (WellSAT) WSCC is an online assessment tool that allows schools to evaluate the alignment of their policies with the WSCC model. This study assesses the usability of the WellSAT WSCC. METHODS: Using a convergent mixed methods design, we collected qualitative and quantitative data from 5 school-based participants with roles in development and evaluation of policy. Participants explored the platform while engaging in a think-aloud procedure and scored a sample policy using the platform. They also completed the System Usability Scale and responded to open-ended questions about the usability of the platform. RESULTS: Participants rated the WellSAT WSCC as an above-average user experience, but data suggested several areas for improvement, including improved instructions, enhanced visual design of the platform, and guidance for subsequent policy changes. CONCLUSION: The WellSAT WSCC provides an above-average user experience but can be improved to increase user experience. These improvements increase the potential for greater use to facilitate integration of the WSCC model into school policy. © 2023, American School Health Association.
Keywords: WSCC model; WellSAT WSCC; dept.hms; peer-reviewed; school health; school policy; whole child

Do maturation, anthropometrics and leg muscle qualities influence repeated change of direction performance in adolescent boys and girls? - Giuriato, M.; Pellino, V.C.; Lovecchio, N.; Codella, R.; Vandoni, M.; Talpey, S. (Biology of Sport, 2023)
The ability to change direction rapidly is a key fitness quality especially in invasive sports where young players perform approximately 300 changes of direction in a game. There is currently limited understanding of how anthropometric characteristics and maturation status influence change of direction ability in adolescent. Therefore, the purpose of this investigation is to assess the influence of anthropometrics and maturation status on change of direction ability in young people. The study involved 706 adolescents (367 girls) aged 14-19-year-old attending the same high school in Northern Italy. Stature, body mass, seated height and leg length were measured to determine the anthropometrics and maturation status of the participants. Repeated change of direction ability (10 × 5 m shuttle run test), lower limb power and muscle strength were evaluated using field tests from the Eurofit test battery. Maturity offset was calculated separately for boys and girls, in accord with the equation proposed by Mirwald. Preliminary analysis with 10 × 5 m as a dependent variable and sex and PHV as a fixed factor, suggests a significant difference between sex (p < 0.001; d = 0.35) but not with PHV (p = 0.986; d = 0.000) and interaction PHV × sex (p = 0.836; d = 0.000). Our results suggested that repeated change of direction performance was influenced by anthropometrics, maturation and muscle qualities in adolescent boys and girls. © 2023 Institute of Sport. All rights reserved.
Keywords: Adolescent; Change of Direction; Eurofit Test; Peak Height Velocity; Speed; dept.hms; peer-reviewed

Physical Activity, Sleep, and Screen Time in Children and Adolescents Before and During the COVID-19 Pandemic: An Analysis of the 2019-2020 National Survey of Children’s Health - Friel, C.P.; Diaz, K.M.; Rupp, K. (American Journal of Health Promotion, 2023)
The COVID-19 pandemic led to unprecedented changes in people’s lifestyles across the United States, but the extent to which the pandemic affected health behaviors of children and adolescents (i.e., physical activity, screen-time, and sleep) is not well understood. These behaviors hold particular significance because of their association with health outcomes. Purpose: The purpose of this study was to examine whether engagement in health behaviors changed from pre-pandemic (2019) to during the pandemic (2020). Methods: The combined 2019-2020 National Survey of Children’s Health (NSCH) was used to inform this study. The NSCH is an annual survey designed to provide national estimates of key indicators of childhood health and well-being. Physical activity (number of days/week with >60 min of activity), screen-time (hours/day of TV viewing and computer use), and sleep (hours/day) were assessed by parental report. Adjusted binomial and multinomial logistic regression models were used to determine the association between survey year and health behaviors. Results: Children and adolescents were 36% more likely to be physically inactive in 2020 compared to 2019. Additionally, children and adolescents were 14% more likely to meet sleep guidelines and 39% less likely to meet screen-time guidelines in 2020 compared to 2019, independent of age, sex, race/ethnicity, and poverty level. Children (6-13 year) and adolescents (14-17 years) were 10% and 15% less likely to get below the recommended amount of sleep in 2020 compared to 2019, respectively. Conclusion: Prevalence of meeting sleep guidelines increased among children and adolescents in 2020 but decreased for physical activity and screen-time. Initiatives targeting activity and screen-time may be urgently needed. Whether rates of these health behaviors return to pre-pandemic levels over the next few years should be closely assessed. © The Author(s) 2023.
Keywords: adolescents; children; dept.hms; health behaviors; peer-reviewed; physical activity; screen time; sedentary behavior; sleep

Effects of an adapted physical education training package on special education teacher instruction - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis (Behavioral Interventions, 2019)
This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low-incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.
Keywords: dept.hms; functional motor skills; peer-reviewed; prompting; reinforcement; severe disabilities; special education

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Pre-Competition Anxiety and Self-Confidence of Wheelchair Basketball Players from China, Taiwan and Hong Kong. - Yang, Jinjin (2005)
Keywords: dept.hms; faculty_collection

Sabbatical leave follow-up report Spring 2019 - Fede, Marybeth H. (2019)
Keywords: dept.hms; faculty_collection; sabbatical_report

The Essentials of Teaching Health Education: Curriculum, Instruction, and Assessment - Benes, Sarah (Human Kinetics, 2016)
"The Essentials of Teaching Health Education presents a skills-based approach to teaching K-12 health education--one that will prepare your students for success in school and beyond. You'll learn practical approaches to putting the contents in action and rely on an array of teaching and assessment strategies." --Publisher's website.
Keywords: Curricula; Health education; Standards; Training of; United States; United States; Health education; United States; Health education teachers; dept.hms; faculty_collection

The Lives and Travels of Mormon & Moroni - Ainsworth, Jerry L. (Peacemakers Pub., 2000)
Keywords: Biography; Mormon (Book of Mormon figure); Moroni (Book of Mormon figure); Book of Mormon; dept.hms; faculty_collection

Understanding health behaviors, weight perceptions, and body appreciation of young adult women engaged in the body positivity movement - Rupp, Kristie; McCoy, Stephanie M. (Women's Health Issues, 2023)
Background The body positivity movement on social media is thought to foster body appreciation, but pervasive societal concern persists about the body positivity movement and the body image, health behaviors, and “normalization of obesity” of young adult women. Purpose This study explored the relationship between engagement in the body positivity movement on social media and weight status, body appreciation, body dissatisfaction, and the health behaviors of intuitive eating and physical activity in young adult women (18–35 years). Methods Participants (N = 521; ∼64% engaged in body positivity content on social media) were recruited using Qualtrics online panels for this cross-sectional survey during February 2021. Outcomes included weight status, weight consideration, weight perception, body appreciation, body dissatisfaction, physical activity, and intuitive eating. Logistic and linear regression models adjusted for age, race, ethnicity, education level, and household income were used to assess the association between engagement in the body positivity movement and specified outcomes. Results Engagement in body positivity content was associated with greater body dissatisfaction (β = 2.33, t(519) = 2.90 p = .017), body appreciation (β = 0.26, t(519) = 2.90 p = .004), and greater likelihood of reporting high amounts of physical activity (odds ratio = 2.28; p < .05) relative to nonengaged peers; these associations remained significant after further adjustment for weight status. Body positivity was not associated with weight status, weight perception, or intuitive eating. Conclusions Engagement in the body positivity movement is associated with higher body dissatisfaction and body appreciation in young adult women, which suggests they may be drawn to and engage in the body positivity movement as a protective or coping mechanism for body dissatisfaction.
Keywords: dept.hms; peer-reviewed

Exertional heat illness: adoption of policies and influencing contextual factors as reported by athletic administrators - Scarneo-Miller, Samantha E.; Adams, William M.; Coleman, Kelly A.; Lopez, Rebecca M. (Sports Health, 2023)
Background:Little is known about the adoption by athletic administrators (AAs) of exertional heat illness (EHI) policies, and the corresponding facilitators and barriers of such policies within high school athletics. This study describes the adoption of comprehensive EHI policies by high school AAs and explores factors influencing EHI policy adoption.Hypothesis:We hypothesized that <50% of AAs would report adoption of an EHI policy, and that the most common facilitator would be access to an athletic trainer (AT), whereas the most common barrier would be financial limitations.Study Design:Cross-sectional.Level of Evidence:Level 4.Methods:A total of 466 AAs (82.4% male; age, 48 ± 9 years) completed a validated online survey to assess EHI prevention and treatment policy adoption (11 components), as well as facilitators and barriers to policy implementation. Access to athletic training services was ascertained by matching the participants? zip codes with the Athletic Training Locations and Services Project. Policy adoption, facilitators, and barriers data are presented as summary statistics (proportions, interquartile range (IQR)). A Welch t test evaluated the association between access to athletic training services and EHI policy adoption.Results:Of the AAs surveyed, 77.9% (n = 363) reported adopting a written EHI policy. The median of EHI policy components adopted was 5 (IQR = 1,7), with only 5.6% (n = 26) of AAs reporting adoption of all policy components. AAs who had access to an AT (P = 0.04) were more likely to adopt a greater number of EHI-related policies, compared with those without access to an AT. An AT employed at the school was the most frequently reported facilitator (36.9%).Conclusion:Most AAs reported having written EHI policy components, and access to an AT resulted in a more comprehensive policy.Clinical Relevance:Employment of an AT within high school athletics may serve as a vital component in facilitating the adoption of comprehensive EHI policies.
Keywords: dept.hms; peer-reviewed

An 8-week peer health coaching intervention among college students: a pilot randomized study - Yan, Zi; Peacock, Jessica; Cohen, Juliana F. W.; Kurdziel, Laura; Benes, Sarah; Oh, Seungbin; Bowling, April (Nutrients, 2023)
This study explored the effects of an 8-week peer coaching program on physical activity (PA), diet, sleep, social isolation, and mental health among college students in the United States. A total of 52 college students were recruited and randomized to the coaching (n = 28) or the control group (n = 24). The coaching group met with a trained peer health coach once a week for 8 weeks focusing on self-selected wellness domains. Coaching techniques included reflective listening, motivational interviews, and goal setting. The control group received a wellness handbook. PA, self-efficacy for eating healthy foods, quality of sleep, social isolation, positive affect and well-being, anxiety, and cognitive function were measured. No interaction effects between time and group were significant for the overall intervention group (all p > 0.05), while the main effects of group difference on moderate PA and total PA were significant (p < 0.05). Goal-specific analysis showed that, compared to the control group, those who had a PA goal significantly increased vigorous PA Metabolic Equivalent of Task (METs) (p < 0.05). The vigorous METs for the PA goal group increased from 1013.33 (SD = 1055.12) to 1578.67 (SD = 1354.09); the control group decreased from 1012.94 (SD = 1322.943) to 682.11 (SD = 754.89); having a stress goal significantly predicted a higher post-coaching positive affect and well-being, controlling the pre-score and other demographic factors: B = 0.37 and p < 0.05. Peer coaching showed a promising effect on improving PA and positive affect and well-being among college students.
Keywords: dept.hms; diet; mental health; peer-reviewed; physical activity; positive affect; sleep; stress

Perception of moderate-intensity physical activity by onset of obesity: A randomized crossover trial - Rupp, Kristie; Stewart, Andrea L.; Friel, Ciarán P. (Clinical Obesity, 2022)
Moderate-intensity physical activity is recommended for inactive adults with overweight/obesity (OW/OB). The objective of this study is to determine if differences exist in the selection of moderate intensity between inactive adults with juvenile-onset (JO) and adult-onset (AO) OW/OB. Participants (JO = 18, AO = 20) were stratified by onset and completed two separate 20-minute moderate-intensity exercise sessions on a treadmill and cycle ergometer (randomized order). Multiple linear regression was used to determine whether exercise intensity (average METS, % age-predicted HRmax), self-reported pleasure or exertion differed by onset, controlling for age and gender. On the treadmill, JO and AO participants selected an average intensity of (mean [SD]) 3.5 (0.9) and 3.7 (0.9) METS, and 64.0 (7.7) and 64.9 (7.5) % of age-predicted HRmax, respectively. On the cycle, JO and AO participants selected an average intensity of 3.3 (0.9) and 3.3 (1.0) METS, and 65.2 (8.8) and 60.7 (7.2) % of age-predicted HRmax. After adjustment, participant intensity selection did not significantly differ by obesity onset when walking or cycling. There were no significant differences in pleasure or perceived exertion by onset, however, perception of exertion was on the high-end of moderate for both the cycle (13.0, 12.5) and treadmill (12.0, 12.1), in JO and AO participants, respectively. Perception of moderate intensity did not differ by obesity onset. Self-selected intensity was at the low end of moderate for walking and cycling.
Keywords: dept.hms; exercise enjoyment; overweight; peer-reviewed; perceived exertion; self-selected intensity; weight loss

Discriminative ability of lower limb strength and power measures in lacrosse athletes - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; Maloney, Maggie; Newman, Thomas; Cordone, Jason; O’Grady, Mathew (International Journal of Sports Medicine, 2023)
The objective of this investigation was to compare isokinetic strength, countermovement jump and drop jump variables between high-contributors and low-contributors within NCAA Division I Men’s and Women’s lacrosse athletes. Men’s (N=36) and Women’s (N=30) NCAA Division I lacrosse athletes completed strength testing of the quadriceps and hamstring across three speeds (60°·s−1, 180°·s−1, 300°·s−1), countermovement and drop jumps. To determine the discriminative ability of select lower-limb strength and power characteristics participants were categorized as high-contributors (Males N=18, age=20.3±0.4 yrs, height=183.9±5.5 cm, mass=90.8±5.8 kg; Females N=15, age=20.8±0.8 yrs, height=169.3±6.7 cm, mass=64.1±7.2 kg) or low-contributors (Males N=18, age=19.5±0.2 yrs, height=184.1±5.6 cm; mass=87.9±8.1 kg; Females N=15, age=19.7±0.2 yrs, height=169.8±7.0 cm, mass=62.9±7.7 kg ) based upon the number of games the participants competed in during the regular season. Within the male cohort, moderate significant (p−1 (d=0.69) and peak power in countermovement jump (d=0.68). Within the women’s cohort a large (d=0.87) significant difference (p−1. Hamstring strength and lower-limb power are important strength measures for lacrosse performance and should be prioritized in training prescription for lacrosse athletes.
Keywords: Key words countermovement jump; dept.hms; drop jump; female athlete; peer-reviewed; performance

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Combining MRI and cognitive evaluation to classify concussion in university athletes - Ly, Monica T.; Scarneo-Miller, Samantha E.; Lepley, Adam S.; Coleman, Kelly; Hirschhorn, Rebecca; Yeargin, Susan; Casa, Douglas J.; Chen, Chi-Ming (Brain Imaging and Behavior, 2022)
Current methods of concussion assessment lack the objectivity and reliability to detect neurological injury. This multi-site study uses combinations of neuroimaging (diffusion tensor imaging and resting state functional MRI) and cognitive measures to train algorithms to detect the presence of concussion in university athletes. Athletes (29 concussed, 48 controls) completed symptom reports, brief cognitive evaluation, and MRI within 72 h of injury. Hierarchical linear regression compared groups on cognitive and neuroimaging measures while controlling for sex and data collection site. Logistic regression and support vector machine models were trained using cognitive and neuroimaging measures and evaluated for overall accuracy, sensitivity, and specificity. Concussed athletes reported greater symptoms than controls (∆R2 = 0.32, p < .001), and performed worse on tests of concentration (∆R2 = 0.07, p < .05) and delayed memory (∆R2 = 0.17, p < .001). Concussed athletes showed lower functional connectivity within the frontoparietal and primary visual networks (p < .05), but did not differ on mean diffusivity and fractional anisotropy. Of the cognitive measures, classifiers trained using delayed memory yielded the best performance with overall accuracy of 71%, though sensitivity was poor at 46%. Of the neuroimaging measures, classifiers trained using mean diffusivity yielded similar accuracy. Combining cognitive measures with mean diffusivity increased overall accuracy to 74% and sensitivity to 64%, comparable to the sensitivity of symptom report. Trained algorithms incorporating both MRI and cognitive performance variables can reliably detect common neurobiological sequelae of acute concussion. The integration of multi-modal data can serve as an objective, reliable tool in the assessment and diagnosis of concussion.
Keywords: Classification; Concussion; Diffusion tensor imaging (DTI); Mild traumatic brain injury (mTBI); Resting state functional MRI; dept.hms; peer-reviewed

Exercise modifications and strategies to enhance shoulder function - Ronai, P. (Strength and Conditioning Journal, 2005)
The purposes of this article are to identify exercise performance-related factors that may contribute to shoulder pain and dysfunction and to describe appropriate training strategies for promoting shoulder stability and enhanced function. This article is not intended to help the reader diagnose and treat injuries or prescribe therapeutic interventions. Strength and conditioning professionals should encourage injured clients to consult a physician, physical therapist, or other appropriate health care professional before starting a conditioning program. © National Strength and Conditioning Association.
Keywords: Exercise technique; Flexibility; Posture; Rotator cuff impingement; Scapular stability; Sensorimotor control; Strength; dept.hms

Resistance training for persons with osteoarthritis and rheumatoid arthritis - Ronai, P.; Sorace, P.; LaFontaine, T. (Strength and Conditioning Journal, 2008)
Arthritic conditions affect more than 40 million americans and are a major cause of physical disability. Resistance training has been found to improve muscular performance in persons with osteoarthritis and rheumatoid arthritis. This column discusses the benefits of resistance training in persons with osteoarthritis and rheumatoid arthritis and provides general suggestions for developing safe, effective resistance training programs. © National Strength and Conditioning Association.
Keywords: dept.hms

Peripheral arterial disease: Exercise is medicineTM - Sorace, P.; Ronai, P.; Churilla, J.R. (ACSM's Health and Fitness Journal, 2010)
Learning objective: Peripheral arterial disease (PAD) significantly affects quality of life, particularly when doing activities such as walking and climbing stairs. In addition, persons with PAD have an increased risk for heart disease, stroke, and limb amputations. This article will summarize PAD, address exercise benefits specific to the disease, and discuss exercise training for those with PAD in both the clinical and the health and fitness setting. © 2010 Lippincott Williams & Wilkins.
Keywords: Claudication; Functional Ability; Resistance Training; Stair Climbing; Walking; dept.hms

Proteins and amino acids: The repair blocks and their place in growth and recovery - Rodriguez, N.R.; Lunn, W. (Nutrient Timing: Metabolic Optimization for Health, Performance, and Recovery, 2011)
Keywords: dept.hms

Weightlifting movements from full extension: The snatch and clean - DiSanto, M.; Valentine, G.; Boutagy, N. (Strength and Conditioning Journal, 2015)
Weightlifting movements require sufficient body speed to squat down and catch the barbell. Body speed can only be maximized if the correct positions are reached before the turnover and catch phases. The snatch from full extension (SFFE) and the clean from full extension (CFFE) allow the athlete to transition from the full extension position to a quick squat underneath the barbell. The SFFE and CFFE can be included into the warm-up or cooldown periods of a training session, focusing on the respective lifts. Correct body positions and speed, as opposed to barbell load, should be emphasized.
Keywords: Body speed; Clean; Full extension; Snatch; Weightlifting; dept.hms

Associations Between Ankle-Brachial Index and Cognitive Function: Results From the Lifestyle Interventions and Independence for Elders Trial - Espeland, M.A.; Newman, A.B.; Sink, K.; Gill, T.M.; King, A.C.; Miller, M.E.; Guralnik, J.; Katula, J.; Church, T.; Manini, T.; Reid, K.F.; McDermott, M.M.; et al. (Journal of the American Medical Directors Association, 2015)
Objective: The objective of this study was to evaluate cross-sectional and longitudinal associations between ankle-brachial index (ABI) and indicators of cognitive function. Design: Randomized clinical trial (Lifestyle Interventions and Independence for Elders Trial). Setting: Eight US academic centers. Participants: A total of 1601 adults ages 70-89 years, sedentary, without dementia, and with functional limitations. Measurements: Baseline ABI and interviewer- and computer-administered cognitive function assessments were obtained. These assessments were used to compare a physical activity intervention with a health education control. Cognitive function was reassessed 24 months later (interviewer-administered) and 18 or 30 months later (computer-administered) and central adjudication was used to classify individuals as having mild cognitive impairment, probable dementia, or neither. Results: Lower ABI had a modest independent association with poorer cognitive functioning at baseline (partial r= 0.09; P < .001). Although lower baseline ABI was not associated with overall changes in cognitive function test scores, it was associated with higher odds for 2-year progression to a composite of either mild cognitive impairment or probable dementia (odds ratio 2.60 per unit lower ABI; 95% confidence interval 1.06-6.37). Across 2 years, changes in ABI were not associated with changes in cognitive function. Conclusion: In an older cohort sedentary individuals with dementia and with functional limitations, lower baseline ABI was independently correlated with cognitive function and associated with greater 2-year risk for progression to mild cognitive impairment or probable dementia. © 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Aged; Aged, 80 and over; Ankle Brachial Index; Ankle-brachial index; Article; Cognition; Cognitive function; Cross-Sectional Studies; Dementia; Disability Evaluation; Exercise; Female; Geriatric Assessment; Health Education; Humans; Male; Mini Mental State Examination; Peripheral artery disease; Sedentary Lifestyle; United States; aged; ankle brachial index; clinical trial; cognition; controlled study; cross-sectional study; dementia; dept.hms; disability; episodic memory; executive function; exercise; female; follow up; geriatric assessment; health education; human; human experiment; learning; longitudinal study; male; mild cognitive impairment; multicenter study; normal human; physical activity; physical performance; randomized controlled trial; recall; sedentary lifestyle; spatial orientation; very elderly; working memory

Lower Wingate Test Power Outcomes from "all-Out" Pretest Pedaling Cadence Compared with Moderate Cadence - Lunn, W.R.; Zenoni, M.A.; Crandall, I.H.; Dress, A.E.; Berglund, M.L. (Journal of Strength and Conditioning Research, 2015)
The aim of the present study was to determine the effect of different pretest pedaling cadences on power outcomes obtained during the Wingate Anaerobic Test (WAnT). Vigorously exercising adult men (n 14, 24.9 ± 1.2 years) and women (n 14, 20.4 ± 0.6 years) participated in a randomized crossover study during which they performed the 30-second WAnT on a mechanically braked cycle ergometer (0.075 kg·kg-1 body weight) under 2 conditions. Participants pedaled maximally with an unloaded flywheel during 5 seconds before resistance was applied and the test began (FAST). In another trial, participants maintained a moderate cadence (80 revolutions per minute [rpm]) during 5 seconds before the test began (MOD). All other components of the WAnT were identical. Peak power (PP), mean power (MP), minimum power (MinP), fatigue index (%FAT), and maximum cadence during test were recorded. Comparisons were made using a 2 × 2 factorial repeated-measures analysis of variance. Regardless of gender, the FAST condition resulted in 22.2% lower PP (612.6 ± 33.0 W vs. 788.3 ± 43.5 W), 13.3% lower MP (448.4 ± 22.2 W vs. 517.2 ± 26.4 W), 11.7% lower MinP (280.9 ± 14.8 W vs. 318.3 ± 17.2 W), and 9.0% lower %FAT (53.5 ± 1.3% vs. 58.8 ± 1.5%) than MOD condition (p < 0.01; mean ± SD). Similar outcomes were observed within gender. The authors conclude that practitioners of the WAnT should instruct participants to maintain a moderate pedal cadence (∼80 rpm) during 5 seconds before the test commences to avoid bias from software sampling and peripheral fatigue. Standardizing the pretest pedal cadence will be important to exercise testing professionals who compare data with norms or generate norms for specific populations. © 2015 National Strength and Conditioning Association.
Keywords: Adult; Bicycling; Cross-Over Studies; Exercise; Exercise Test; Fatigue; Female; Humans; Male; Young Adult; adult; anaerobic; controlled study; crossover procedure; cycling; dept.hms; ergometry; exercise; exercise test; fatigue; female; human; male; muscle; pathophysiology; peer-reviewed; physiology; procedures; randomized controlled trial; young adult

Association of accelerometry-measured physical activity and cardiovascular events in mobility-limited older adults: The LIFE (Lifestyle Interventions and Independence for Elders) study - Cochrane, S.K.; Chen, S.-H.; Fitzgerald, J.D.; Dodson, J.A.; Fielding, R.A.; King, A.C.; McDermott, M.M.; Manini, T.M.; Marsh, A.P.; Newman, A.B.; Pahor, M.; Tudor-Locke, C.; et al. (Journal of the American Heart Association, 2017)
Background--Data are sparse regarding the value of physical activity (PA) surveillance among older adults-particularly among those with mobility limitations. The objective of this study was to examine longitudinal associations between objectively measured daily PA and the incidence of cardiovascular events among older adults in the LIFE (Lifestyle Interventions and Independence for Elders) study. Methods and Results--Cardiovascular events were adjudicated based on medical records review, and cardiovascular risk factors were controlled for in the analysis. Home-based activity data were collected by hip-worn accelerometers at baseline and at 6, 12, and 24 months postrandomization to either a physical activity or health education intervention. LIFE study participants (n=1590; age 78.9±5.2 [SD] years; 67.2% women) at baseline had an 11% lower incidence of experiencing a subsequent cardiovascular event per 500 steps taken per day based on activity data (hazard ratio, 0.89; 95% confidence interval, 0.84-0.96; P=0.001). At baseline, every 30 minutes spent performing activities ≥500 counts per minute (hazard ratio, 0.75; confidence interval, 0.65-0.89 [P=0.001]) were also associated with a lower incidence of cardiovascular events. Throughout follow-up (6, 12, and 24 months), both the number of steps per day (per 500 steps; hazard ratio, 0.90, confidence interval, 0.85-0.96 [P=0.001]) and duration of activity ≥500 counts per minute (per 30 minutes; hazard ratio, 0.76; confidence interval, 0.63-0.90 [P=0.002]) were significantly associated with lower cardiovascular event rates. Conclusions--Objective measurements of physical activity via accelerometry were associated with cardiovascular events among older adults with limited mobility (summary score > 10 on the Short Physical Performance Battery) both using baseline and longitudinal data. © 2017 The Authors.
Keywords: Accelerometry; Actigraphy; Age Factors; Aged; Aged, 80 and over; Aging; Article; Cardiovascular; Cardiovascular Diseases; Exercise; Exercise Therapy; Female; Fitness Trackers; Geriatric Assessment; Health Knowledge, Attitudes, Practice; Humans; Incidence; Male; Mobility Limitation; Patient Education as Topic; Physical activity; Predictive Value of Tests; Prognosis; Protective Factors; Risk Factors; Risk Reduction Behavior; Time Factors; United States; accelerometry; actimetry; activity tracker; age; aged; aging; attitude to health; cardiovascular disease; cardiovascular risk; clinical study; clinical trial; confidence interval; controlled study; dept.hms; devices; exercise; female; follow up; geriatric assessment; hazard ratio; health education; human; incidence; kinesiotherapy; lifestyle; major clinical study; male; medical record review; morbidity; multicenter study; patient education; phase 3 clinical trial; physical activity; physical mobility; predictive value; priority journal; prognosis; protection; randomized controlled trial; risk factor; risk reduction; time factor; very elderly; walking difficulty

Sports Injury Prevention: The Role of the Strength and Conditioning Coach - Talpey, S.W.; Siesmaa, E.J. (Strength and Conditioning Journal, 2017)
Prevention of sports injuries is a priority for sport stakeholders across the spectrum of training and competition. Achieving this objective requires a multidisciplinary approach with strength and conditioning coaches playing an important role in the process. When considering sports injury prevention strategies, the role of the strength and conditioning coach can extend beyond observing exercise technique and prescribing training to develop a robust and resilient athlete. This paper provides strength and conditioning coaches with a broad overview of the sports injury prevention process and outlines examples of how strength and conditioning coaches can work to promote and improve athlete safety. © 2017 National Strength and Conditioning Association.
Keywords: Coaching; Sport safety; Sports medicine; dept.hms

Before-school physical activity program's impact on social and emotional learning - Goh, T.L.; Leong, C.H.; Fede, M.; Ciotto, C. (Journal of School Health, 2022)
BACKGROUND: Despite the positive impact of social and emotional learning (SEL) on the emotional well-being of children, literature on physical activity engagement and SEL among this population has been limited. Therefore, the purpose of this study was to examine whether school students' SEL would improve after participation in a before-school physical activity program. METHODS: A total of 138 fourth and sixth grade students from 1 elementary school and 1 middle school participated in this study. Seventy-five students participated in the before-school physical activity program, while 63 students were in the control group. The physical education teachers implemented the program 3 days per week, for 3 weeks. The participants completed a 10-question adapted Devereux Student Strengths Assessment-Mini before and after the program. Repeated measures ANOVA was run to determine the effects of the program on SEL competence. RESULTS: The fourth and sixth grade students who participated in the program reported a 7 and 10% improvement in pre- versus post-intervention SEL competence, respectively. Students in the control group reported no change in their SEL competence. CONCLUSION: Considering the benefits of a before-school physical activity program on students' SEL, stakeholders should consider including more physical activity programming within school policies. © 2022 American School Health Association.
Keywords: dept.hms; peer-reviewed

Heart rate recovery, central systolic pressure, and augmentation index in young healthy individuals - Latchman, P.L.; Yang, Q.; Kong, L.; Zhang, H.; Sebagisha, J.; De Meersman, R.E. (Vascular Health and Risk Management, 2022)
Purpose: Measuring heart rate recovery (HRR) holds valuable cardiovascular information and requires minimal technical skill and cost. Understanding the associations between HRR and more robust cardiovascular indicators, such as central systolic blood pressure (CSBP), can provide valuable cardiovascular information with less involvement. CSBP is a strong predictor of certain cardiovascular diseases. The study aims to examine the association between measures of HRR and CSBP and the augmentation index (AIx) in a group of young, healthy individuals and based on sex. Participants and Methods: One-hundred and seven participants (men – 55, women – 52) were measured for HRR at one minute (HRR1) and two minutes (HRR2) after maximum oxygen consumption (VO2max) testing, CSBP, and the AIx at a heart rate of 75 beats∙min−1 (AIx@75). Results: The Pearson correlation indicated no association between HRR1, HRR2, and CSBP in men and women combined: r = 0.06, P = 0.53; r = 0.05, P = 0.59, respectively, or based on sex: men = r = 0.01, P = 0.95; r = 0.04, P = 0.79, respectively, and women = r = −0.05, P = 0.75; r = −0.09, P = 0.52, respectively. However, there were associations between HRR1 and AIx@75 in men and women combined: r = −0.37, P < 0.001, and based on sex: men = r = −0.31, P = 0.02, and women = r = −0.38, P < 0.01. Conclusion: Measures of HRR were not associated with CSBP in a combined group of young men and women or based on sex. Most measures of HRR, especially those established by parasympathetic nervous activity, were associated with lower AIx@75. Though measures of HRR might be good indicators of cardiovascular disease, they might not be good indicators of CSBP in young, healthy individuals. © 2022 Latchman et al.
Keywords: Article; Blood Pressure; Cardiovascular Diseases; Cardiovascular System; Female; Heart Rate; Humans; Male; adult; augmentation index; blood pressure; cardiovascular disease; cardiovascular parameters; cardiovascular system; central systolic pressure; cholinergic system; controlled study; dept.hms; diastolic blood pressure; female; heart rate; heart rate recovery; heart rate variability; human; human experiment; male; maximal oxygen uptake; normal human; peer-reviewed; predictive value; sex difference; systolic blood pressure; young adult

Changes in health behaviors associated with weight gain by weight classification during the COVID-19 pandemic. - Rupp, Kristie; Friel, Ciarán P (American journal of health promotion : AJHP, 2021)
Purpose: To determine whether perceived changes (i.e. perception of engagement during the pandemic relative to pre-pandemic) in specific health behaviors differ by weight status (i.e. healthy weight, overweight, obese). Design: Cross-sectional. Recruitment took place between June-August 2020, via social media posts and Qualtrics online panels. Setting: Participants completed the survey online through the Qualtrics platform. Sample: Analyses included N = 502 participants (≥18 years); 45.2% healthy weight (n = 227), 28.5% overweight (n = 143), and 26.3% obese (n = 132). Measures: Study-specific survey items included questions about demographics and perceived changes in health behaviors. Analysis: Logistic regression models, adjusted for age, race, ethnicity, gender, education, and COVID-19 diagnosis, assessed the odds of perceiving changes in health behaviors considered a risk for weight gain. Results: Participants with obesity, but not overweight, were significantly more likely to report deleterious changes to health behaviors compared to healthy weight peers, including: (1) decreased fruit/vegetable consumption [adjusted odds ratio (AOR) = 1.92; 95% confidence interval (CI): (1.13, 3.26)]; (2) increased processed food consumption [AOR = 1.85; 95%CI: (1.15, 3.00)]; (3) increased caloric intake [AOR = 1.66; 95% CI: (1.06, 2.61)]; (4) decreased physical activity [AOR = 2.07; 95%CI: (1.31, 3.28)]; and (5) deterioration in sleep quality [AOR = 2.07; 95%CI: (1.32, 3.25)]. Conclusion: Our findings suggest that adults with obesity may be at greater risk for unhealthy behaviors during a period of prolonged social distancing, potentially exacerbating the obesity epidemic. © The Author(s) 2021.
Keywords: COVID-19; COVID-19 Testing; Cross-Sectional Studies; Health Behavior; Humans; Pandemics; SARS-CoV-2; Sleep Quality; Weight Gain; body weight gain; cross-sectional study; dept.hms; health behavior; human; pandemic; peer-reviewed; sleep quality

Athletic training employment in secondary schools by geographic setting and school size within the United States. - Suzuki-Yamanaka, Miwako; Huggins, Robert A.; Armstrong, Kirk J.; Coleman, Kelly A.; Casa, Douglas J.; Kaneoka, Koji (Journal of athletic training, 2021)
Context: The Athletic Training Locations and Services (ATLAS) Annual Report suggested that athletic trainer (AT) employment status differed based on geographic locale. However, the influence of geographic locale and school size on AT employment is unknown. Objective: To determine if differences existed in the odds of having AT services by locale for public and private schools and by student enrollment for public schools. Design: Cross-sectional study. Setting: Public and private secondary schools with athletics programs. Patients or Other Participants: Data from 20 078 US public and private secondary schools were obtained. Main Outcome Measures(s): Data were collected by the ATLAS Project. Athletic trainer employment status, locale (city, suburban, town, or rural) for public and private schools, and school size category (large, moderate, medium, or small) only for public schools were obtained. The employment status of ATs was examined for each category using odds ratios. Logistic regression analysis produced a prediction model. Results: Of the 19 918 public and private schools with available AT employment status and locale, suburban schools had the highest access to AT services (80.1%) with increased odds compared with rural schools (odds ratio = 3.55 [95% CI = 3.28, 3.85]). Of 15 850 public schools with known AT employment status and student enrollment, large schools had the highest rate of AT services (92.1%) with nearly 18.5 times greater odds (odds ratio = 18.49 [95% CI = 16.20, 21.08]) versus small schools. The logistic model demonstrated that the odds of access to an AT increased by 2.883 times as the school size went up by 1 category. Conclusions: Nationally, suburban schools and large public schools had the greatest access to AT services compared with schools that were in more remote areas and with lower student enrollment. These findings elucidate the geographic locales and student enrollment levels with the highest prevalence of AT services. Ó by the National Athletic Trainers’ Association, Inc
Keywords: adult; article; athletic trainer; athletics; controlled study; cross-sectional study; dept.hms; employment status; female; high school; human; male; outcome assessment; peer-reviewed; prediction; prevalence; training

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine

The effects of a 10-week, periodized, off-season resistance-training program and creatine supplementation among collegiate football players. - Wilder, Nathan; Gilders, Roger; Hagerman, Frederick; Deivert, Richard G (Journal of strength and conditioning research, 2002)
The periodized resistance-training model has not been well documented in the literature. Further research is needed to determine if periodized resistance training in conjunction with creatine supplementation can cause changes in strength, performance, total body weight, girth, and lean muscle mass. Therefore, the purpose of this investigation was to determine the effects of periodized resistance training in conjunction with low-dose (LD) and high-dose (HD) creatine supplementation on strength, body composition, and anaerobic muscular endurance. Subjects were divided into 3 groups: LD, HD, and placebo (P). Testing took place pre-, mid-, and postsupplementation for the following: weight, body composition (fat-free mass and fat mass), 1 repetition maximum squat, and anaerobic muscular endurance testing. Results revealed no significant differences in either creatine group when compared with the P group. However, significant differences were noted over time. These data suggest that 10 weeks of periodized resistance training was effective for causing changes in strength, body composition, and anaerobic muscular endurance.
Keywords: *Creatine/ad [Administration & Dosage]; *Dietary Supplements; *Exercise/ph [Physiology]; *Football; Adolescent; Adult; Anaerobiosis; Anthropometry; Body Composition; Body Weight; Creatine; Dietary Supplements; Exercise; Football; Humans; Male; Muscle, Skeletal; Muscle, Skeletal/ph [Physiology]; Periodization; Physical Endurance; Resistance training; Single-Blind Method; Supplementation; adolescence; adult; anaerobic growth; anthropometry; article; athlete; body composition; body weight; controlled study; creatine; dept.hms; diet supplementation; exercise; football; human; male; muscle exercise; muscle mass; muscle strength; normal human; peer-reviewed; performance; physical stress; physiology; single blind procedure; skeletal muscle; supplementation; training; ❓ Multiple DOI

Effects of sprint interval training and body weight reduction on power to weight ratio in experienced cyclists. - Lunn, William R; Finn, Joan A; Axtell, Robert S (Journal of strength and conditioning research, 2009)
The purpose of this study was to determine the effect of supramaximal sprint interval training (SIT), body weight reduction, and a combination of both treatments on peak and average anaerobic power to weight ratio (PPOan:Wt, APOan:Wt) by manipulating peak and average anaerobic power output (PPOan, APOan) and body weight (BW) in experienced cyclists. Participants (N = 34, age = 38.0 +/- 7.1 years) were assigned to 4 groups for a 10-week study. One group performed twice-weekly SIT sessions on a cycle ergometer while maintaining body weight (SIT). A second group did not perform SIT but intentionally reduced body weight (WR). A third group simultaneously performed SIT sessions and reduced body weight (SIT+WR). A control group cycled in their normal routine and maintained body weight (CON). The 30-second Wingate Test assessed pretest and posttest POan:Wt scores. There was a significant mean increase (p < 0.05) from pretest to posttest in PPOan:Wt and APOan:Wt (W x kg(-1)) scores in both SIT (10.82 +/- 1.71 to 11.92 +/- 1.77 and 8.05 +/- 0.64 to 8.77 +/- 0.64, respectively) and WR (10.33 +/- 2.91 to 11.29 +/- 2.80 and 7.04 +/- 1.45 to 7.62 +/- 1.24, respectively). PPOan and APOan (W) increased significantly only in SIT (753.7 +/- 121.0 to 834.3 +/- 150.1 and 561.3 +/- 62.5 to 612.7 +/- 69.0, respectively). Body weight (kg) decreased significantly in WR and SIT + WR (80.3 +/- 13.7 to 75.3 +/- 11.9 and 78.9 +/- 10.8 to 73.4 +/- 10.8, respectively). The results demonstrate that cyclists can use SIT sessions and body weight reduction as singular training interventions to effect significant increases in anaerobic power to weight ratio, which has been correlated to enhanced aerobic cycling performance. However, the treatments were not effective as combined interventions, as there was no significant change in either PPOan:Wt or APOan:Wt in SIT + WR.
Keywords: *Bicycling/ph [Physiology]; *Physical Education and Training/mt [Methods]; *Weight Loss; Adult; Analysis of Variance; Bicycling; Body Composition; Body Mass Index; Body Weight; Female; Humans; Male; Physical Education and Training; Physical Endurance; Physical Endurance/ph [Physiology]; Reproducibility of Results; Weight Loss; Wingate test; adult; analysis of variance; article; bicycle; body composition; body mass; body weight; dept.hms; endurance; female; human; male; methodology; peer-reviewed; physical education; physiology; reproducibility; weight reduction

The performance-level model of hospital decontamination preparedness. - Phelps, Scot; Doering, Garrett (American journal of disaster medicine, 2008)
OBJECTIVE: Describe a multilevel model of decontamination capacity for hospitals., DESIGN: Descriptive model., SETTING: Acute care hospitals with decontamination responsibilities., PATIENTS, PARTICIPANTS: None., INTERVENTIONS: None., MAIN OUTCOME MEASURE(S): None., RESULTS: This multilevel model of defining decontamination capacity would allow more realistic assessment of current capacity, allow for fluctuating service levels depending on time of day, incorporate realistic ramp-up and ramp-down of decontamination services, allow for a defined fall-back decontamination model should decontamination processes fail, allow hospitals to define long-term decontamination service level goals, and allow better understanding of when and why to focus on low-risk/low-resource patients rather than high-risk/high-resource patients., CONCLUSIONS: This multiple-level model would allow for more realistic and effective hospital-based decontamination service models and should become part of the national decontamination paradigm.
Keywords: *Decontamination/st [Standards]; *Disaster Planning/st [Standards]; *Emergency Service, Hospital/og [Organization & Administration]; *Hospital Administration/st [Standards]; *Models, Organizational; Decontamination; Disaster Planning; Emergency Service, Hospital; Hospital Administration; Hospitals; Hospitals/st [Standards]; Humans; MLCS; MLOWN; Models, Organizational; Terrorism; article; dept.hms; disaster planning; emergency health service; hospital; hospital management; human; nonbiological model; organization and management; standard; terrorism; waste management

Tell Me What You See: An Arts-Based Health Education Program for Youth. - Edmondson, Bonnie (Health Promotion Practice, 2021)
A cross-sector collaboration among a community-based organization, a prison arts program, and state departments of Public Health, Education, and Correction was established to address critical health education prevention efforts for at-risk high school-aged youth. The Tell Me What You See initiative utilizes artwork and poetry created by incarcerated youth to promote sexually transmitted disease (STD), HIV, and hepatitis prevention with students in public high schools and juvenile justice facilities. This innovative intervention integrates functional health knowledge and skills-based education through an art-based interdisciplinary approach reaching various populations of youth in multiple settings across a state. Evaluation results indicated that the materials effectively engage youth and open up a critical dialogue among peers and adults by addressing the role personal behavior can have in the prevention of STDs, hepatitis, and HIV. Lessons learned and recommendations are provided., (C)2021Sage Publications
Keywords: Adolescent; Adult; Child; Educational Status; HIV/AIDS; Health Education; Health Promotion; Humans; STDs; Schools; Sexually Transmitted Diseases; adolescent; adolescent health; adult; arts; arts in public health; arts-based education; behavior change; child; community organization; creative arts; dept.hms; educational status; health education; health promotion; hepatitis; human; incarcerated youth; juvenile justice; partnerships; peer-reviewed; public health; school; school health; sexually transmitted disease

Physical activity participation, flourishing and academic engagement in adolescents with obesity. - McCoy, Stephanie; Rupp, Kristie (Pediatric Obesity, 2021)
Background: Adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. However, it is unknown how participation in physical activity influences flourishing and academic engagement in adolescents with obesity. The current study examined engagement in varying levels of physical activity and the likelihood of flourishing and academic engagement in adolescents with obesity. Methods: Analyses included 26 764 adolescents, ages 10–17 years, from the parent-reported, combined 2016–2017 National Survey of Children's Health. Participants were grouped by physical activity levels (none, low, moderate, daily). Outcome variables included flourishing (finishing tasks, staying calm when faced with a challenge and showing interest in new things) and academic engagement (completing all required homework and caring about doing well in school). Logistic regression models, adjusted for age, sex, race, household income, highest level of education in the household, behavioural conduct problems and depression assessed the likelihood of each outcome comparing physical activity levels among adolescents with obesity. Results: Adolescents with obesity who participated in any amount of physical activity (low, moderate and daily) or sports had significantly greater likelihood of flourishing and academic engagement compared those that did not engage in any physical activity (p's ¡ 0.05). Conclusions: Participation in even low amounts of physical activity or participation in sports increases the likelihood of flourishing and academic engagement in adolescents with obesity, which expands on previous findings that adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. © 2021 World Obesity Federation
Keywords: Adolescent; Child; Exercise; Health Status; Humans; Pediatric Obesity; Schools; adolescence; adolescent; child; childhood obesity; dept.hms; exercise; flourishing; health status; human; obesity; peer-reviewed; physical activity; school

Chocolate milk and endurance exercise recovery: protein balance, glycogen, and performance. - Lunn, William R; Pasiakos, Stefan M; Colletto, Megan R; Karfonta, Kirstin E; Carbone, John W; Anderson, Jeffrey M; Rodriguez, Nancy R (Medicine and science in sports and exercise, 2012)
Purpose: This study examined effects of fat-free chocolate milk (MILK) consumption on kinetic and cellular markers of protein turnover, muscle glycogen, and performance during recovery from endurance exercise. Methods: Male runners participated in two trials separated by 1 wk and consumed either MILK or a nonnitrogenous isocaloric carbohydrate (CHO) control beverage (CON) after a 45-min run at 65% of V̇O 2peak. Postexercise muscle protein fractional synthetic rate (FSR) and whole-body protein turnover were determined during 3 h of recovery using muscle biopsies and primed constant infusions of L-[ring-H5]phenylalanine and L-[1-C]leucine, respectively. Phosphorylation of translational signaling proteins and activity of proteolytic molecules were determined using Western blotting and enzymatic activity assays. Muscle glycogen was quantified, and treadmill time to exhaustion was determined after the recovery period. Results: Consuming MILK after exercise resulted in higher mixed muscle FSR with lower whole-body proteolysis and synthesis compared with CON (P ≤ 0.05). Phosphorylation of eIF4E-BP1 and FOXO3a was higher for MILK (P < 0.01), whereas Akt phosphorylation was lower during recovery regardless of dietary treatment (P < 0.05). Enzymatic activity assays indicated lower caspase-3 activity during recovery for MILK (P < 0.01) and higher 26S proteasome activity for CON (P < 0.01). Muscle glycogen was not affected by either dietary treatment; however, time to exhaustion was greater for MILK than for CON (P < 0.05). Conclusions: The effects of consumption of MILK after endurance exercise on FSR, signaling molecules of skeletal muscle protein turnover, leucine kinetics, and performance measures suggest unique benefits of milk compared with a CHO-only beverage. © 2012 by the American College of Sports Medicine.
Keywords: *Athletic Performance/ph [Physiology]; *Cacao/me [Metabolism]; *Milk/me [Metabolism]; *Muscle Proteins/bi [Biosynthesis]; *Physical Endurance/ph [Physiology]; ATP dependent 26S protease; Adaptor Proteins, Signal Transducing; Adaptor Proteins, Signal Transducing/me [Metabolism]; Adult; Animals; Athletic Performance; Cacao; Cell Cycle Proteins; Dietary Carbohydrates; Dietary Carbohydrates/me [Metabolism]; EIF4EBP1 protein, human; FOXO3 protein, human; Forkhead Box Protein O3; Forkhead Transcription Factors; Forkhead Transcription Factors/me [Metabolism]; Glycogen; Glycogen/an [Analysis]; Heart Rate; Heart Rate/ph [Physiology]; Humans; Male; Milk; Muscle Proteins; Muscle, Skeletal; Muscle, Skeletal/ch [Chemistry]; Muscle, Skeletal/me [Metabolism]; Muscle, Skeletal/ph [Physiology]; Oxygen Consumption; Oxygen Consumption/ph [Physiology]; Phosphoproteins; Phosphoproteins/me [Metabolism]; Phosphorylation; Physical Endurance; Proteasome Endopeptidase Complex; Proteasome Endopeptidase Complex/an [Analysis]; Protein synthesis; Proto-Oncogene Proteins c-akt; Proto-Oncogene Proteins c-akt/me [Metabolism]; Young Adult; adult; animal; article; athletic performance; biosynthesis; cacao; carbohydrate diet; chemistry; dept.hms; endurance; forkhead transcription factor; glycogen; heart rate; human; intracellular signaling; leucine kinetics; male; metabolism; milk; muscle glycogen; muscle protein; oxygen consumption; peer-reviewed; phosphoprotein; phosphorylation; physiology; proteasome; protein kinase B; proteolysis; signal transducing adaptor protein; skeletal muscle; time to exhaustion

Gradual vs. Maximal Acceleration: Their Influence on the Prescription of Maximal Speed Sprinting in Team Sport Athletes. - Young, Warren B; Duthie, Grant M; James, Lachlan P; Talpey, Scott W; Benton, Dean T; Kilfoyle, Anthony (Sports, 2018)
The primary purpose of this study was to determine if a difference existed between peak speed attained when performing a sprint with maximal acceleration versus from a gradual build-up. Additionally, this investigation sought to compare the actual peak speed achieved when instructed to reach 75% and 90% of maximum speed. Field sport athletes (n = 21) performed sprints over 60 m under the experimental conditions, and the peak speed was assessed with a radar gun. The gradual build-up to maximum speed (8.30 +/- 0.40 m.s-1) produced the greater peak speed (effect size = 0.3, small) than the maximum acceleration run (8.18 +/- 0.40 m.s-1), and the majority of participants (62%) followed this pattern. For the sub-maximum runs, the actual mean percentage of maximum speed reached was 78 +/- 6% for the 75% prescribed run and 89 +/- 5% for the 90% prescription. The errors in attaining the prescribed peak speeds were large (~15%) for certain individuals, especially for the 75% trial. Sprint training for maximum speed should be performed with a gradual build-up of speed rather than a maximum acceleration. For sub-maximum interval training, the ability to attain the prescribed target peak speed can be challenging for field sport athletes, and therefore where possible, feedback on peak speeds reached should be provided after each repetition.
Keywords: Acceleration; Conditioning; Programming; Team sport; dept.hms; peer-reviewed

A PEP grant’s influence on change in a school district: One year post funding - Egan, Cate A.; Abel-Berei, Catherine P.; Karp, Grace Goc (Evaluation and program planning, 2021)
This study examined teachers' and administrators' perceptions of the institutionalization phase of the Carol M. White Physical Education for Progress (PEP) grant. A qualitative exploratory single case study (Yin, 2014) was utilized to examine the elements of the PEP grant that sustained or did not sustain after its conclusion, along with elements that were institutionalized and influences on this process. The findings were represented in the following three themes: (a) positive shifts, (b) backsliding, and (c) new directions, each with their own subthemes. Positive shifts includes sub-themes: (a) philosophy, (b) instruction, assessment and curriculum, (c) collaboration, and (d) respect. Backsliding includes sub-themes: (a) wellness team functioning, (b) the loss of PD and collaboration time, and (c) reduced data collection. New directions includes sub-themes: (a) mastery learning, (b) during school physical activity, (c) stress, and (d) administrative support. The factors that were institutionalized were quality physical education leadership roles, change in teachers' philosophies that influenced their instruction and assessment, and garnered administrative support. These elements were embedded into the physical education program and the school so much so that principals now expect the same type of programming from any new hire. Copyright © 2021 Elsevier Ltd. All rights reserved.
Keywords: administration; administrative personnel; article; curriculum; dept.hms; funding; health education; human; human experiment; institutional framework; institutionalization; leadership; learning; peer-reviewed; perception; philosophy; physical activity; physical education; physiological stress; primary education; single-case study; student; teacher; teaching

Current activities centered on healthy living and recommendations for the future: A position statement from the HL-PIVOT network - Arena, Ross; Myers, Jonathan; Kaminsky, Leonard A.; Williams, Mark A.; Sabbahi, Ahmad; Popovic, Dejana; Axtell, Robert S.; Faghy, Mark A.; Hills, Andrew P.; Olivares, Silvia Lizett Olivares; Lopez, Mildred; Pronk, Nicolaas P.; et al. (Current Problems in Cardiology, 2021)
We continue to increase our cognizance and recognition of the importance of healthy living (HL) behaviors and HL medicine (HLM) to prevent and treat chronic disease. The continually unfolding events precipitated by the coronavirus disease 2019 (COVID-19) pandemic have further highlighted the importance of HL behaviors, as indicated by the characteristics of those who have been hospitalized and died from this viral infection. There has already been recognition that leading a healthy lifestyle, prior to the COVID-19 pandemic, may have a substantial protective effect in those who become infected with the virus. Now more than ever, HL behaviors and HLM are essential and must be promoted with a renewed vigor across the globe. In response to the rapidly evolving world since the beginning of the COVID-19 pandemic, and the clear need to change lifestyle behaviors to promote human resilience and quality of life, the HL for Pandemic Event Protection (HL-PIVOT) network was established. The 4 major areas of focus for the network are: (1) knowledge discovery and dissemination; (2) education; (3) policy; (4) implementation. This HL-PIVOT network position statement provides a current synopsis of the major focus areas of the network, including leading research in the field of HL behaviors and HLM, examples of best practices in education, policy, and implementation, and recommendations for the future. © 2021 Elsevier Inc.
Keywords: Biomedical Research; COVID-19; Cardiorespiratory Fitness; Chronic Disease; Diabetes Mellitus; Diet; Exercise; Health Education; Health Policy; Healthy; Healthy Lifestyle; Humans; Implementation Science; Information Dissemination; Obesity; Patient Education as Topic; Quality of Life; Review; Risk Reduction Behavior; SARS-CoV-2; Sedentary Behavior; Smoking Cessation; Type 2; body mass; cardiorespiratory fitness; chronic disease; coronavirus disease 2019; dept.hms; education; epidemiology; exercise; health; health behavior; health care personnel; health care planning; health care policy; health education; health promotion; healthy diet; healthy lifestyle; healthy living medicine; human; information dissemination; knowledge; knowledge discovery; law; lifestyle; medical research; medicine; non insulin dependent diabetes mellitus; nutrition; obesity; pandemic; patient education; peer-reviewed; physical activity; psychological resilience; quality of life; risk reduction; sedentary lifestyle; sleep; smoking cessation; syndemic; unhealthy lifestyle behavior

Stakeholders’ perspectives on the effects of a PEP grant on a district-wide CSPAP - Abel-Berei, Catherine P.; Karp, Grace Goc; Fennell, Marcis; Drake, Elisa M.; Olsen, Simon (Journal of Teaching in Physical Education, 2021)
A Comprehensive School Physical Activity Program (CSPAP) can help children be physically active for 60 min/day. Physical Education for Progress grants provided opportunities to improve physical education and physical activity programming. Purpose: This study explored stakeholders' perspectives on the effects of a Physical Education for Progress grant on a district-wide CSPAP. Method: Stakeholders included physical educators (n = 10; K-12), administrators (n = 6), and one superintendent. Individual, semistructured interviews were used to examine how the grant affected stakeholders' perspectives of the CSPAP. Results: The grant affected the CSPAP by providing (a) opportunities for professional development, (b) opportunities to establish a K-12 curriculum map, and (c) access to equipment and resources. Discussion: Framed in social ecological theory, intrapersonal, interpersonal, institutional, and community levels were influenced by the grant. Interactions between levels enabled changes in all CSPAP components, especially quality PE. Conclusion: A Physical Education for Progress grant is a successful mechanism to enhance a district-wide CSPAP. © 2021 Human Kinetics, Inc.
Keywords: dept.hms; peer-reviewed

Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Promoting healthy ageing through light volleyball intervention in Hong Kong: study protocol for a randomised controlled trial - Leung, Ka Man; Chung, Pak-Kwong; Chan, Aileen W. K.; Ransdell, Lynda; Siu, Parco Ming Fai; Sun, Ping; Yang, Jinjin; Chen, Tie Cheng (Bmc Sports Science Medicine and Rehabilitation, 2020)
Background: Our pilot study has demonstrated improvements in health outcomes through participation in a new sport, light volleyball (LVB), among older adults. In response to the promising results of the LVB pilot study and the priority of allocating resources to the prevention of age-related fitness degradation by the Hong Kong (HKG) government, the present study aims to investigate the effectiveness of a LVB intervention on physical and psychological health attributes among older adults at a larger scale in HKG. Methods/design: This study will apply both quantitative and qualitative methods with a large sample (approximately 315 participants). We will adopt a randomized controlled trial (RCT) design to further evaluate the effectiveness of a LVB intervention on health outcomes against a comparison group, Tai Chi (TC), and a control group (C). Older adults will be eligible to join the intervention if they are (a) aged 65 years and above; (b) living in the community independently; (c) absent of diagnosed cognitive impairment; (d) not regular participants in a structured PA program for two years preceding the study; and (e) able to achieve a passing score on the Timed-up-and-go test (TUG) and Abbreviated Mental Test (AMT). About 315 participants will be randomly assigned into 3 groups in 1:1:1 ratio. LVB group participants will receive 16-week LVB program; TC group will utilize a simplified 24-form Yang Style TC, and C group participants will be instructed to maintain their normal daily activity and join regular non-exercise social gatherings. Measurements will be collected before and after the intervention, and 6 months and 12 months after completion of the intervention. Discussion: This intervention, if effective, will enhance older adult's physical and psychological health, and provide the data and evidence to support policymaking in relation to future PA promotion for older adults. Trial registration number: ChiCTR1900026657. © 2020 The Author(s).
Keywords: Adapted sport; Age-related fitness degradation; Ageing; Article; Hong Kong; Physical activity; Tai Chi; aged; clinical effectiveness; clinical trial protocol; cognitive defect; controlled study; dept.hms; healthy aging; human; major clinical study; mental health; mental test; peer-reviewed; physical activity; qualitative research; quantitative study; randomized controlled trial; timed up and go test; volleyball

Differences in health behaviors related to overweight/obesity by race/ethnicity in a diverse urban commuter college - Rupp, Kristie; Schnoll, Roseanne; Zigmont, Victoria A. (Journal of American College Health, 2020)
Objective: To examine health behaviors associated with overweight/obesity by race/ethnicity at a diverse urban college. Participants: 270 undergraduates (77.0% female; 26.7% non-Hispanic white) and median body mass index (BMI) of 23.1 kg/m2. Methods: A questionnaire about health-related behaviors as part of the “Get Fruved” project was used to measure health behaviors (sugar sweetened beverage (SSB), fruit and vegetable consumption, physical activity, stress, and sleep) by race/ethnicity. Multivariable logistic regression was used to assess the adjusted odds of engaging in positive health-related behaviors. Results: Non-Hispanic black and Hispanic students were 64% and 59% less likely to consume lower amounts of SSB. Hispanic students were 83% and 81% less likely to meet vegetable and fruit recommendations. Non-Hispanic black and other (including biracial) had reduced odds of meeting vegetable recommendations (AOR = 0.18 and 0.28). Conclusions: Disparities in SSB, fruit, and vegetable consumption represent potential intervention targets to improve health behaviors among racial/ethnic minorities. © 2020 Taylor & Francis Group, LLC.
Keywords: College; dept.hms; dept.pch; health behavior; peer-reviewed; race/ethnicity

Reducing sedentary behavior versus increasing moderate-to-vigorous intensity physical activity in older adults: a 12-week randomized, clinical trial - Gibbs, Bethany Barone; Brach, Jennifer S.; Byard, Tom; Creasy, Seth; Davis, Kelliann K.; McCoy, Stephanie; Peluso, Anna; Rogers, Renee J.; Rupp, Kristie; Jakicic, John M. (Journal of Aging and Health, 2016)
Objective: To compare the effects of behavioral interventions targeting decreased sedentary behavior versus increased moderate-to-vigorous intensity physical ac...
Keywords: dept.hms

Managing ball retrieval in skill practice situations - Webb, Daniel; Kozub, Francis M; Yang, Jinjin (Strategies, 2003)
Keywords: dept.hms

A focus group study of DES daughters: implications for health care providers. - Duke, Suzanne S; Mcgraw, Sarah A; Avis, Nancy E; Sherman, Amanda (Psycho-oncology, 2000)
A focus group study of women exposed to diethylstiibestrol (DES) in utero (DES daughters) was conducted to gain understanding about exposure to this drug from a patient perspective. Focus group participants reported that learning about their DES exposure was devastating; they experienced strains in their family relationships, emotional shock, a feeling that their health concerns were not appreciated by others and, to some degree, a sense of social isolation. Although many were aware of the need for special gynecological exams and high-risk prenatal care, they were frustrated by what they felt was a lack of reliable and clear information about the effects of DES exposure. Most expressed questions and anxiety about their health. Many found their communication with physicians about their DES exposure unsatisfying. They felt that physicians lacked information about the long-term health effects of DES exposure and as a result did not give them accurate information. Furthermore, they felt that physicians were dismissive of their concerns and often gave what they felt to be false reassurances. Consequently, the women developed an enduring distrust of the medical profession. The results of the study suggest implications for the delivery of health care to DES daughters. Copyright (C) 2000 John Wiley & Sons, Ltd.
Keywords: *Abnormalities, Drug-Induced/px [Psychology]; *Carcinogens/ae [Adverse Effects]; *Diethylstilbestrol/ae [Adverse Effects]; *Focus Groups; *Genitalia, Female/de [Drug Effects]; *Nuclear Family/px [Psychology]; *Stress, Psychological/et [Etiology]; Abnormalities, Drug-Induced; Adult; Carcinogens; Diethylstilbestrol; Female; Focus Groups; Genitalia, Female; Human; Humans; Life Change Events; New York; Nuclear Family; Physician-Patient Relations; Self-Help Groups; Stress, Psychological; Support, U.S. Gov't, P.H.S.; adenocarcinoma; adult; anxiety; article; awareness; clinical article; clinical research; dept.hms; diethylstilbestrol; doctor patient relation; drug exposure; emotional stress; female; health care delivery; health education; health promotion; human; life event; patient counseling; patient education; patient satisfaction; physician attitude; prenatal care; risk assessment; social isolation; vagina cancer

Exposure to diethylstilbestrol: design of a multilevel community intervention - Duke, Suzanne S.; McGraw, Sarah A.; Avis, Nancy E. (Health Promotion Practice, 2000)
The planning of community health education interventions aimed at multiple levels is complex and challenging. This challenge is increased when a primary audience is difficult to reach. Individuals who were exposed to diethylstilbestrol (DES) decades ago represent a difficult-to-reach audience because they are not always aware of their exposure or the health risks of their exposure. However, DES-exposed individuals need specific screening and health care. An intervention was developed to increase awareness about DES in Nassau County, New York to address this concern. The Precede-Proceed Model was used to develop distinct intervention strategies to reach the general public, which includes individuals who may not be aware that they were exposed; those who are aware of their exposure but may not be following recommended health care practices; and community physicians. Behavioral targets, determining factors, and intervention goals were identified for each group. Specific intervention strategies were planned and implemented for each target audience. Addressing three target audiences simultaneously may produce a synergistic effect, enhancing program impact. © 2000, Sage Publications. All rights reserved.
Keywords: dept.hms; peer-reviewed

Sensitivity to sensoriprocessing, self-discrepancy, and emotional reactivity of collegiate athletes. - Kemler, David S (Perceptual and Motor Skills, 2006)
This study investigated how differences between athletes who scored low and high on sensoriprocessing sensitivity apply self-discrepancies and emotional reactions to competitive sporting events. Two hypotheses were proposed: The High Sensitivity group (n = 33) would score higher for anxiety, guilt, and shame, and lower on pride and report more stress attributed to self-discrepancies than the Low Sensitivity group (n = 32) following competitive sports events. Collegiate varsity athletes were administered the High Sensitivity Scale prior to competition and completed the Selves Questionnaire and the Goal Congruent and Incongruent Emotion Scale immediately after competition. Scores for the High Sensitivity Scale were used to separate athletes into high and low sensitivity groups. A multivariate analysis of variance and subsequent univariate analyses indicated that the High Sensitivity group reported higher scores on anxiety, shame, and stress than the Low Sensitivity group. This was interpreted as reflecting differences between both ideal and ought self-discrepancies.
Keywords: *Affect; *Cognition/ph [Physiology]; *Self Concept; *Sensation/ph [Physiology]; *Sports/px [Psychology]; *Universities; Adult; Affect; Awareness; Cognition; Female; Humans; Male; Psychological Theory; Questionnaires; Self Concept; Sensation; Sports; Surveys and Questionnaires; Universities; adult; affect; article; awareness; cognition; dept.hms; female; human; male; physiology; psychological aspect; psychological theory; questionnaire; self concept; sensation; sport; university

Actigraphy features for predicting mobility disability in older adults - Kheirkhahan, Matin; Tudor-Locke, Catrine; Axtell, Robert; Buman, Matthew P.; Fielding, Roger A.; Glynn, Nancy W.; Guralnik, Jack M.; King, Abby C.; White, Daniel K.; Miller, Michael E.; Siddique, Juned; Brubaker, Peter; et al. (Physiological Measurement, 2016)
Actigraphy has attracted much attention for assessing physical activity in the past decade. Many algorithms have been developed to automate the analysis process, but none has targeted a general model to discover related features for detecting or predicting mobility function, or more specifically, mobility impairment and major mobility disability (MMD). Men (N = 357) and women (N = 778) aged 70-89 years wore a tri-axial accelerometer (Actigraph GT3X) on the right hip during free-living conditions for 8.4 +/- 3.0 d. One-second epoch data were summarized into 67 features. Several machine learning techniques were used to select features from the free-living condition to predict mobility impairment, defined as 400 m walking speed ¡0.80 m s(-1). Selected features were also included in a model to predict the first occurrence of MMD-defined as the loss in the ability to walk 400 m. Each method yielded a similar estimate of 400 m walking speed with a root mean square error of similar to 0.07 m s(-1) and an R-squared values ranging from 0.37-0.41. Sensitivity and specificity of identifying slow walkers was approximately 70% and 80% for all methods, respectively. The top five features, which were related to movement pace and amount (activity counts and steps), length in activity engagement (bout length), accumulation patterns of activity, and movement variability significantly improved the prediction of MMD beyond that found with common covariates (age, diseases, anthropometry, etc). This study identified a subset of actigraphy features collected in free-living conditions that are moderately accurate in identifying persons with clinically-assessed mobility impaired and significantly improve the prediction of MMD. These findings suggest that the combination of features as opposed to a specific feature is important to consider when choosing features and/or combinations of features for prediction of mobility phenotypes in older adults.
Keywords: Accelerometers; Actigraphy; Analysis process; Artificial intelligence; Data mining; Disability; Feature extraction; Forecasting; Free livings; General model; Learning systems; Living conditions; Mean square error; Older adults; Patient monitoring; Physical activity; Sedentary; Walking aids; Walking speed; aging; data mining; dept.hms; disability; machine learning; physical activity; sedentary; ⚠️ Invalid DOI

Great games that disappeared - Rauschenbach, James; Swartz, Daniel R (Strategies: a journal for physical and sport educators, 2016)
Sometimes through a single person's efforts, a new and innovative game is developed and promoted locally. Occasionally, circumstances cause these games to remain on a local level without being adopted by mainstream physical educators and physical activity professionals. Unfortunately, some educators tend to stick to what they know and teach traditional games and sports. This practice has left little room for unique and innovative games such as tchoukball and hocker to contribute to physical education curriculum. This article describes the history of how each of these games was developed and promoted. Rules, equipment and game-play strategies are provided. ©, Copyright Taylor & Francis.
Keywords: dept.hms

Psychoanalysis, artistic obsession, and artistic motivation: the study of pathography. - Kemler, David S (Perceptual and Motor Skills, 2014)
A modern assessment of Freud's conceptualization of the creative process focusing on drives, ego psychology, and object relation theory is presented. 40 artists and musicians were interviewed employing 13 open-ended questions to provoke responses historically associated with the theoretical conceptualizations of Freud and post-Freudian theory related to the creative process. Creative process was defined as internal object relations that motivate the external connection between artist and the creative work. Measured responses concerning purpose and understanding; motivation before, during, and after performance; obstacles in performance; and needs through the creative process were assessed. Cluster analysis segregated the participants into high, medium, and low agreement groups based on similarity of responses. A multivariate stepwise regression revealed four questions (enlightenment, drives, obstacles, and ought self discrepancies) accounted for 83.9% of the variance. A post hoc discriminant function analysis identified 82.5% of the population to their correct groups. The findings support Spitz's (2005) suggestion that we regard “drives, ego psychology, and object relation theory not as separate approaches but as parts of a whole with varying stresses or accents” (p. 503).
Keywords: Adult; Art; Cluster Analysis; Creativity; Drive; Female; Freudian Theory; Humans; Male; Middle Aged; Motivation; Multivariate Analysis; Music; Object Attachment; Obsessive Behavior; Psychoanalytic Theory; Regression Analysis; adult; art; article; cluster analysis; creativity; dept.hms; drive; female; human; male; middle aged; motivation; multivariate analysis; music; object relation; obsession; psychoanalytic theory; psychological aspect; regression analysis

Spontaneous baroreflex sensitivity in young normotensive African-American women - Latchman, Peter; Gates, Gregory J; Axtell, Robert S; Pereira, Jason; Bartels, Matthew N; Meersman, Ronald Edmond De (Clinical Autonomic Research, 2013)
Keywords: African American; European American; adult; article; body mass; breathing rate; clinical article; controlled study; dept.hms; diastolic blood pressure; family history; female; human; hypertension; physical activity; pressoreceptor reflex; race difference; systolic blood pressure

Make your own fitness: the suspension training project - Rauschenbach, Jim; Morrell, Katie; Ridley, Ben; Walsh, Brittany (Strategies: a journal for physical and sport educators, 2013)
Keywords: dept.hms

Promoting physical activity for elders with compromised function: the Lifestyle Interventions and Independence for Elders (LIFE) Study physical activity intervention - Rejeski, W. Jack; Axtell, Robert; Fielding, Roger; Katula, Jeffrey; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; Pahor, Marco; Rego, Alvito; Tudor-Locke, Catrine; Newman, Mark; Walkup, Michael P.; et al. (Clinical Interventions in Aging, 2013)
The Lifestyle Interventions and Independence for Elders (LIFE) Study is a Phase III randomized controlled clinical trial (Clinicaltrials.gov identifier: NCT01072500) that will provide definitive evidence regarding the effect of physical activity (PA) on major mobility disability in older adults (70-89 years old) who have compromised physical function. This paper describes the methods employed in the delivery of the LIFE Study PA intervention, providing insight into how we promoted adherence and monitored the fidelity of treatment. Data are presented on participants' motives and self-perceptions at the onset of the trial along with accelerometry data on patterns of PA during exercise training. Prior to the onset of training, 31.4% of participants noted slight conflict with being able to meet the demands of the program and 6.4% indicated that the degree of conflict would be moderate. Accelerometry data collected during PA training revealed that the average intensity - 1,555 counts/minute for men and 1,237 counts/minute for women - was well below the cutoff point used to classify exercise as being of moderate intensity or higher for adults. Also, a sizable subgroup required one or more rest stops. These data illustrate that it is not feasible to have a single exercise prescription for older adults with compromised function. Moreover, the concept of what constitutes “moderate” exercise or an appropriate volume of work is dictated by the physical capacities of each individual and the level of comfort/stability in actually executing a specific prescription.
Keywords: Accelerometry; Aged; Aged, 80 and over; Aging; Compromised physical function; Exercise; Female; Health Promotion; Humans; Independent Living; Male; Mobility Limitation; Older adults; Physical disability; Qualitative Research; Risk Reduction Behavior; Sex Distribution; accelerometry; aged; aging; article; autoregulation; body mass; compromised physical function; computer interface; computer program; conceptual framework; controlled study; dept.hms; education; elderly care; ethnicity; exercise intensity; female; health education; human; human experiment; lifestyle; male; motor performance; normal human; older adults; phase 3 clinical trial; physical activity; physical capacity; physical disability; quality of life; randomized controlled trial; semi structured interview; sex difference; social behavior; social environment

“The greatest game ever”: swatball - Swartz, Daniel R; Rauschenbach, Jim (Strategies: a journal for physical and sport educators, 2013)
Keywords: dept.hms

Physical activity strategies for improved cognition: the mind/body connection - Fede, Marybeth H (Strategies: a journal for physical and sport educators, 2012)
Keywords: dept.hms

Potential impact of a 500-mL water bolus and body mass on plasma osmolality dilution - Sollanek, Kurt J.; Kenefick, Robert W.; Cheuvront, Samuel N.; Axtell, Robert S. (European Journal of Applied Physiology, 2011)
A methodological discrepancy exists in the hydration assessment literature regarding the establishment of euhydration, as some investigations utilize a prehydration technique, while others do not (overnight fluid/food fast). However, the degree that plasma osmolality (Posm) dilutes when using the pre-hydration method and how body mass/composition might influence the results is not known. Thirty subjects (22 M, 8 F; 20 ± 2 years (mean ± SD); 1.8 ± 0.1 m; 75.8 ± 13.5 kg) had P osm measured after an 8-h food and fluid fast (overnight fast) and 90 min after a 500-mL (4-9 mL/kg) water bolus (prehydration). From pre- to post-bolus, participants' P osm declined from 297 ± 3.5 to 295 ± 3.8 mmol/kg (p<0.05; Δ -1.7 ± 3.5 mmol/kg). One-third of the sample diluted to more than -3 mmol/kg. The effect of body mass on P osm dilution was investigated by comparing dilution in the ten lightest (62.8 ± 3.4 kg) and heaviest (92.0 ± 9.8 kg) participants; however, the change between the light (Δ -1.9 ± 3.8 mmol/kg) versus heavy groups (Δ -1.1 ± 3.0 mmol/kg) was not different (p>0.05). The correlation between body mass or total body water and change in P osm was weak (p>0.05), as was the correlation between relative fluid intake based on mass and change in P osm (p>0.05). The two methodologies appear to produce similar P osm values when measured in most individuals. However, the potential for significant dilution (>3 mmol/kg) should be considered when choosing the pre-hydration methodology. © Springer-Verlag (outside the USA) 2011.
Keywords: Adolescent; Adult; Blood; Blood Chemical Analysis; Body Weight; Dehydration; Drinking; Female; Fluid intake; Humans; Hydration assessment; Hypohydration; Male; Osmolar Concentration; SCSU-student; Total body water; Water; Water-Electrolyte Balance; Young Adult; adolescent; adult; article; blood; blood analysis; body weight; clinical trial; dehydration; dept.hms; drinking; drug effect; electrolyte balance; female; human; male; metabolism; osmolarity; physiology; water

Impaired autonomic function in normotensive obese children - Latchman, Peter L; Mathur, Madhu; Bartels, Matthew N; Axtell, Robert S; Meersman, Ronald E De (Clinical Autonomic Research, 2011)
Purpose To evaluate baroreflex sensitivity and autonomic control in a cohort of normotensive obese (OB) children. Method A cross-sectional investigation, in which, baroreflex sensitivity and autonomic control were evaluated using transfer function and power spectral density analysis (PSDA) of the electrocardiogram and beat-to-beat blood pressures in normotensive OB children and normal weight normotensive controls. All methods used were noninvasive and data were captured while seated and at rest. Results The OB and control subjects non-obese (NO) were of similar age (OB 9.1 ± 1.9 years vs.NO9.2 ± 1.4 years). The OB group was classified as having a BMI greater than the 95th percentile adjusted for age and gender, and a NO group with a BMI at or less than the 95th percentile (BMI percentile OB. 97.5 ± 1.3 vs. NO 58.5 ± 24.1). Both groups had similar normotensive blood pressures. T tests revealed that baroreflex sensitivity and HFRR were significantly reduced in the OB 9.2 ± 2.7 vs. 15.2 ± 4.7 (ms/mmHg) and 6.7 ± 1.1 vs. 8.2 ± 1.1 ms 2, respectively, while LF SBP and LF/HF ratio were significantly increased in the OB 11.9 ± 5.6 vs. 8.2 ± 4.7 mmHg 2 and 1.2 ± 0.7 vs. 0.54 ± 0.3, respectively. Conclusions Normotensive OB children exhibited significantly reduced baroreflex sensitivity, parasympathetic control as well as increased sympathetic control when compared with healthy, NO controls. Findings in this investigation raise the awareness that autonomic dysfunction is present in young OB normotensive children. © Springer-Verlag 2011.
Keywords: Autonomic Nervous System; Autonomic modulation; Baroreflex sensitivity; Blood Pressure; Child; Cross-Sectional Studies; Female; Humans; Male; Normotensive; Obese children; Obesity; article; autonomic dysfunction; blood pressure; blood pressure measurement; body mass; body weight; child; clinical article; controlled study; dept.hms; electrocardiogram; female; human; male; obesity; pressoreceptor reflex; school child; sensitivity analysis

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed

The association between sympatho-vagal balance and central blood pressures - Latchman, P. L.; Gates, G.; Pereira, J.; Axtell, R. R.; Gardner, K.; Schlie, J.; Yang, Q.; Yue, T.; Morin-Viall, A.; Demeersman, R. (Physiology International, 2020)
Purpose: High central blood pressure is more predictive of cardiovascular disease (CVD) versus high peripheral blood pressure. Measures of central pressures (CPs) include, central systolic blood pressure (CSBP) and central diastolic blood pressure. Measures of central pressures augmentation (CPsA) include augmentation pressure (AP) and the augmentation index @ 75 beats$min-1 (AIx@75). Increased sympathetic tone (ST) is also associated with CVD. The low to high frequency ratio (LF/HF) is often used to determine sympatho-vagal balance. Given the association between ST, CPs, CPsA and CVD there is a need to understand the association between these predictors of CVD. The aims of this study were to examine the association between the LF/HF ratio, CPs, and CPsA in men and women collectively and based on gender. Methods: We measured the LF/HF ratio, CSBP, AP, and AIx@75 in 102 participants (41F/61M). The LF/ HF ratio was determined via power spectral density analysis. CSBP, AP, and AIx@75 were determined via applanation tonometry. Results: The LF/HF ratio was inversely associated with AP (r 5 -0.26) and AIx @75 (r 5 -0.29) in the combined group of men and women. The LF/HF ratio was inversely associated with CSBP (r 5 -0.27), AP (r 5 -0.28), and AIx@75 (r 5 -0.32) in men, but not in women. Conclusion: There is an inverse association between the LF/HF ratio, AP, and AIx@75 in men and women combined. The association between the LF/HF ratio, CSBP, AP, and AIx@75, differs based on gender. © 2020 Akademiai Kiado, Budapest.
Keywords: Adult; Arterial Pressure; Article; Augmentation index; Augmentation pressure; Blood Pressure; Cardiovascular System; Central diastolic blood pressure; Central systolic blood pressure; Electrocardiography; Female; Heart Rate; Humans; Male; Sex Characteristics; Sympathetic Nervous System; Sympatho-vagal balance; Vagus Nerve; Young Adult; adrenergic system; adult; arterial pressure; augmentation index; augmentation pressure; blood pressure; blood pressure measurement; cardiovascular disease; cardiovascular parameters; cardiovascular system; central pressures augmentation; dept.hms; diagnostic imaging; diastolic blood pressure; electrocardiography; female; gender; heart rate; human; low to high frequency ratio; major clinical study; male; pathophysiology; peer-reviewed; physiology; power spectrum; procedures; sexual characteristics; spectroscopy; sphygmomanometry; sympathetic tone; sympatho vagal balance; systolic blood pressure; tonometry; vagus nerve; young adult

Dimensions of burn survivor distress and its impact on hospital length of stay: A national institute on disability, independent living, and rehabilitation research burn model system study. - O'Brien, Kyle H (Burns : journal of the International Society for Burn Injuries, 2020)
OBJECTIVE: Guided by the Transactional Model of Stress and Coping, this study seeks to (1) examine the independent relationships between the level of distress among burn survivors, pre-morbid psychiatric history, and burn severity on length of hospital stay, and (2) to examine the relationship between having a premorbid psychiatric history and level of distress following a burn injury., METHODS: Data collected by the National Institute on Disability, Independent Living, Rehabilitation Research funded Burn Model System (N = 846) was used to theoretically link psychological distress with the length of hospital stay for survivors of burn injuries. Structural Equation Modeling was used to evaluate the aims of this study., RESULTS: Although counterintuitive, and while significant, burn severity was found to have a rather modest association with a burn survivor's level of distress, indicating that one's ability to cope may be a better predictor of distress rather than burn severity alone. Premorbid psychiatric history was significantly associated with increased levels of distress. While burn severity was associated with length of stay, level of distress did not act as a partial mediator. Length of stay was, however, significantly related to having a premorbid-psychiatric history. Of notable interest, a significant racial, ethnic, and gender difference exists in level of distress. Women and people of color experience higher levels of distress holding constant burn severity and psychiatric history., CONCLUSION: A need exists to assess for and address premorbid and current mental health challenges of burn survivors, specifically the ability to cope, especially among people of color and women, regardless of the burn size or severity. Copyright © 2019 Elsevier Ltd and ISBI. All rights reserved.
Keywords: *Adaptation, Psychological; *Burns/px [Psychology]; *Length of Stay/sn [Statistics & Numerical Data]; *Mental Disorders/px [Psychology]; *Psychological Distress; *Stress, Psychological/px [Psychology]; Adaptation, Psychological; Adolescent; Adult; African American; African Americans; African Americans/px [Psychology]; African Americans/sn [Statistics & Numerical Data]; Aged; Aged, 80 and over; Article; Body Surface Area; Burn survivors; Burns; Burns/ep [Epidemiology]; Burns/pa [Pathology]; Burns/pp [Physiopathology]; Caucasian; Distress; Ethnic Groups; European Continental Ancestry Group; European Continental Ancestry Group/px [Psychology]; European Continental Ancestry Group/sn [Statistics & Numerical Data]; Female; Hispanic; Hispanic Americans; Hispanic Americans/px [Psychology]; Hispanic Americans/sn [Statistics & Numerical Data]; Humans; Integrated care; Latent Class Analysis; Length of Stay; Length of stay; Male; Mental Disorders; Mental Disorders/ep [Epidemiology]; Mental health; Middle Aged; Models, Psychological; Psychological Distress; Psychosomatic; Sex Factors; Stress, Psychological; Stress, Psychological/eh [Ethnology]; Stress, Psychological/ep [Epidemiology]; Survivors; Young Adult; adolescent; adult; aged; body surface; burn; burn survivor; coping behavior; dept.hls; dept.hms; dept.rec; distress syndrome; electric burn; ethnic group; ethnology; female; hospital discharge; hospitalization; human; latent class analysis; length of stay; major clinical study; male; mental disease; mental stress; middle aged; outcome assessment; pain severity; pathology; pathophysiology; peer-reviewed; personal experience; psychiatric treatment; psychological aspect; psychological model; psychology; scald; secondary analysis; sex factor; structural equation modeling; survivor; very elderly; wound closure; young adult

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test - Lunn, William R.; Axtell, Robert S. (The Journal of Strength & Conditioning Research, 2019)
Lunn, WR and Axtell, RS. Validity and reliability of the Lode Excalibur Sport cycle ergometer for the Wingate Anaerobic Test. J Strength Cond Res XX(X): 000–000, 2019—Although multiple testing devices advertise Wingate Anaerobic Test (WAnT), capability, reliability, and validity data are sparse. The purpose was to determine whether the Lode Excalibur Sport cycle ergometer is a reliable and valid instrument to conduct the 30-second WAnT when compared with the Monark 894e Peak Bike ergometer. Recreationally active men (n = 49; 20.6 ± 2.5 years; 1.75 ± 0.07 m; and 79.1 ± 9.8 kg) completed four 30-second WAnTs: 2 each on the Lode and the Monark ergometers for peak power (PP), mean power (MP), minimum power (MinP), fatigue index (FI), and peak cadence (vmax) measurement. Interday and interunit correlation, multivariate analysis of variance, regression, and Bland-Altman analysis determined reliability and validity. Cohen's d was used to determine effect size. Relative reliability (intraclass correlation coefficient) with 95% confidence interval for Monark and Lode was very high for PP, MP, MinP, and vmax and high for FI (r > 0.83; coefficient of variation ≤ 27.0%; p < 0.01). Interunit correlation was strong for PP, MP, MinP, and vmax (r > 0.75; p < 0.001) and moderate for FI (p = 0.001). Lode PP and FI values were significantly less (p < 0.001; d > 1.18) and MinP, MP, and vmax significantly greater (p ≤ 0.001; d > 0.51) than Monark. Proportional bias was demonstrated for all variables (p < 0.04; d > 2.68) except vmax. The Lode ergometer reliably provides WAnT outcomes and correlates well to the Monark ergometer. However, differences in power values and proportional bias between differently braked instruments prevent use of the Lode ergometer for comparison of WAnT data with normative data generated by the Monark ergometer.
Keywords: dept.hms; peer-reviewed

Feasibility and safety of a group physical activity program for youth with type 1 diabetes - Ash, Garrett I.; Joiner, Kevin L.; Savoye, Mary; Baker, Julien S.; Gerosa, James; Kleck, Emma; Patel, Neha S.; Sadler, Lois S.; Stults-Kolehmainen, Matthew; Weinzimer, Stuart A.; Grey, Margaret (Pediatric Diabetes, 2019)
Background/ObjectiveMany adolescents with type 1 diabetes do not achieve 60 minutes of daily moderate-to-vigorous intensity physical activity (MVPA). Recognizing the importance of peer influence during adolescence, we evaluated the feasibility and safety of a group MVPA intervention for this population. MethodsEighteen adolescents with type 1 diabetes (age 14.12 .3 years, female 67%, black or Latino 67%, median body mass index 92%ile, A1c 79.925.1 mmol/mol, 9.5 +/- 2.3%). Intervention sessions (35minutes MVPA and 45minutes discussion) occurred 1x/week for 12weeks. Feasibility and safety metrics were enrollment, completion of intervention and assessments, cost, and hypoglycemia rates. Participants completed MVPA (accelerometry), and exploratory nutritional, psychosocial, clinical, and fitness variable assessments at baseline, 3 months, and 7 months. Hedges' effect sizes were calculated. ResultsEnrollment was 16%, and intervention completion was 56%. Assessment completion at 7 months was 67% for MVPA, nutrition, and fitness, 83% for psychosocial assessments, and 94% for clinical assessments. Cost was $1241 per completing participant. One episode of mild hypoglycemia occurred during the sessions (0.6%). Self-reported daily fruit/vegetable servings (d=-0.72) and diabetes self-management behaviors decreased over time (d=-0.40). In the 10 completers, endurance run score improved (d=0.49) from low baseline levels, while systolic blood pressure decreased (d=-0.75) and low-density lipoprotein increased (d=0.49) but stayed within normal ranges. ConclusionsThe protocol for the group MVPA intervention was safe and had some feasibility metrics meriting further investigation. MVPA levels and glycemic control remained suboptimal, suggesting the need for more intensive interventions for this population.
Keywords: Accelerometry; Adolescent; Age Factors; Article; Black person; Blood Glucose; Child; Combined Modality Therapy; Diabetes Mellitus, Type 1; Diet Records; Exercise; Exercise Therapy; Feasibility Studies; Female; Group Processes; Health Behavior; Hispanic; Humans; Male; Young Adult; accelerometry; adolescent; adult; adverse event; age; behavior; blood; body mass; child; clinical article; clinical outcome; clinical protocol; clinical trial; cost; dept.hms; diabetes mellitus; disease severity; endurance; exercise; feasibility study; female; fitness; food intake; fruit; glucose blood level; glycated hemoglobin A; group process; health behavior; health program; human; hypoglycemia; insulin dependent diabetes mellitus; kinesiotherapy; low density lipoprotein; male; medical record; metabolism; multimodality cancer therapy; nutritional assessment; patient safety; peer-reviewed; physical activity; physiology; priority journal; procedures; psychosocial care; scoring system; self care; self report; systolic blood pressure; type 1; vegetable; young adult

Stakeholders' support of CSPAP sustainability after a three-year PEP grant - Egan, Catherine A.; Karp, Grace Goc; Berei, Catherine (Research Quarterly for Exercise and Sport, 2019)
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Sport specialization: A survey of collegiate and professional athletes - Misasi, Sharon P.; Morin, Gary; Swartz, Daniel Reid (Research Quarterly for Exercise and Sport, 2019)
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Changes in Lower Body Muscular Performance Following a Season of NCAA Division I Men’s Lacrosse - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; James, Lachlan (Sports, 2019)
The tactical and technical components of training become a primary emphasis, leaving less time for targeted development of physical qualities that underpin performance during the competition phase of a training program. A deemphasis on physical preparation during the in-season training phase may make athletes more susceptible to injury and decrease performance on the field. Two weeks prior to the start and one week following the conclusion of the 16-week collegiate lacrosse season, lower body force production was assessed in eight National Collegiate Athletic Association (NCAA) Division I Men’s Lacrosse athletes. Lower body force production capabilities were determined via the performance of countermovement jumps (CMJ) and drop jumps (DJ) performed on a force plate and isokinetic strength testing of the quadriceps and hamstring muscle groups across three velocities. Isokinetic strength of the hamstrings and the hamstring to quadriceps strength ratio were maintained or increased over the course of the competition phase of training. Relative peak force obtained from the CMJ and the reactive strength index from the DJ decreased significantly over the season. The maintenance of isokinetic strength and the decrease in CMJ and DJ performance may indicate the presence of neuromuscular fatigue that accumulated over the course of the season.
Keywords: Isokinetic; Power; Reactive strength; Strength; dept.hms; isokinetic; peer-reviewed; power; reactive strength; strength

Bullying perpetration and victimization among adolescents with overweight and obesity in a nationally representative sample - Rupp, Kristie; McCoy, Stephanie M. (Childhood Obesity, 2019)
Keywords: dept.hms; peer-reviewed

A case for promoting movement medicine: preventing disability in the LIFE randomized controlled trial - Fanning, Jason; Rejeski, W Jack; Chen, Shyhhuei; Nicklas, Barbara J; Walkup, Michael P; Axtell, Robert S; Fielding, Roger A; Glynn, Nancy W; King, Abby C; Manini, Todd M; Mcdermott, Mary Mcgrae; Newman, Anne B; et al. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2019)
Background: The movement profile of older adults with compromised function is unknown, as is the relationship between these profiles and the development of major mobility disability (MMD)-a critical clinical outcome. We first describe the dimensions of movement in older adults with compromised function and then examine whether these dimensions predict the onset of MMD. Methods: Older adults at risk for MMD (N = 1,022, mean age = 78.7 years) were randomized to receive a structured physical activity intervention or health education control. We assessed MMD in 6-month intervals (average follow-up of 2.2 years until incident MMD), with activity assessed at baseline, 6-, 12- and 24-month follow-up via accelerometry. Results: A principal components analysis of 11 accelerometer-derived metrics yielded three components representing lifestyle movement (LM), extended bouts of moderate-to-vigorous physical activity (MVPA), and stationary body posture. LM accounted for the greatest proportion of variance in movement (53%). Within health education, both baseline LM (HR = 0.74; 95% CI 0.62 to 0.88) and moderate-to-vigorous physical activity (HR = 0.69; 95% CI 0.54 to 0.87) were associated with MMD, whereas only LM was associated with MMD within physical activity (HR = 0.74; 95% CI 0.61 to 0.89). There were similar nonlinear relationships present for LM in both physical activity and health education (p ¡ .04), whereby risk for MMD was lower among individuals with higher levels of LM. Conclusions: Both LM and moderate-to-vigorous physical activity should be central in treatment regimens for older adults at risk for MMD.
Keywords: Acceleration; Accelerometry; Age Factors; Aged; Aged, 80 and over; Aging; Confidence Intervals; Disability; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Linear Models; Male; Mobility Limitation; Physical Fitness; Physical activity; Prognosis; Sedentary; Sex Factors; Single-Blind Method; Walking Speed; acceleration; age; aged; aging; clinical trial; confidence interval; controlled study; dept.hms; disability; female; fitness; geriatric assessment; human; male; multicenter study; peer-reviewed; physiology; procedures; prognosis; randomized controlled trial; sex factor; single blind procedure; statistical model; very elderly; walking difficulty; walking speed

Evaluating accelerometry thresholds for detecting changes in levels of moderate physical activity and resulting major mobility disability - Rejeski, W. Jack; Walkup, Michael P.; Fielding, Roger A.; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; McDermott, Mary McGrae; Miller, Emily Y; Newman, Anne B.; Tudor-Locke, Catrine; Axtell, Robert S.; Miller, Michael E. (Journals of Gerontology Series A-biological Sciences and Medical Sciences, 2018)
Background: An important decision with accelerometry is the threshold in counts per minute (CPM) used to define moderate to vigorous physical activity (MVPA). We explore the ability of different thresholds to track changes in MVPA due to a physical activity (PA) intervention among older adults with compromised function: 760 CPM, 1,041 CPM, and an individualized threshold. We also evaluate the ability of change in accelerometry and self-reported PA to attenuate treatment effects on major mobility disability (MMD). Methods: Data from a week of hip worn accelerometers and self-reported PA data (30-day recall) were examined from baseline, 6-, 12-, and 24-months of follow-up on 1,528 older adults. Participants were randomized to either PA or Health Education (HE). MMD was objectively defined by loss of ability to walk 400 m during the follow-up. Results: The three thresholds yielded similar and higher levels of MVPA for PA than HE (p ¡ .001), however, this difference was significantly attenuated in participants with lower levels of physical function. Self-reported PA that captured both walking and strength training totally attenuated the intervention effect for MMD, an 18% reduction to a 3% increase. Accelerometer CPMs showed less attenuation of the intervention effect. Conclusions: Accelerometry assessment within the LIFE study was not sensitive to change in level in physical activity for older adults with very low levels of physical function. A combination of self-report and objective measures are recommended for use in physical activity intervention studies of the elderly; limitations of accelerometry deserve closer attention.
Keywords: Accelerometry; Aged; Aged, 80 and over; Female; Geriatric Assessment; Humans; LIFE-study; Male; Mobility Disability; Mobility Limitation; Motor Activity; Older Adults; Thresholds; Walking; accelerometry; aged; clinical trial; controlled study; dept.hms; female; geriatric assessment; human; male; motor activity; multicenter study; peer-reviewed; physiology; procedures; randomized controlled trial; very elderly; walking; walking difficulty

Rating of perceived exertion is a stable and appropriate measure of workload in judo. - Bromley, Sally J; Drew, Michael K; McIntosh, Andrew; Talpey, Scott (Journal of Science and Medicine in Sport, 2018)
OBJECTIVES: Heart rate (HR), blood lactate concentration [La] and/or rating of perceived exertion (RPE) have been utilised to monitor judo training load in technical and randori (competition training) sessions, but are yet to be investigated in mixed sessions containing both elements. Therefore the purpose of this study was to: (1) determine the stability of these variables, and (2) to assess the efficacy of RPE as a load variable for mixed judo sessions., DESIGN: Cross-sectional study., METHODS: Twenty-nine athletes attended two mixed training sessions at an international training camp. Bout and session characteristics, including RPE, physical and mental effort, heart rate (HR) and post-session [La] were recorded. A two-way random-effects intra-class correlation assessed variable stability. Multilevel mixed-effects ordered logistic regression investigated relationships between RPE and other variables for bouts and sessions., RESULTS: Average and minimum HR across sessions correlated highly (ICC=0.95 and 0.94, respectively). Good correlations existed between [La], session-RPE and mental effort, and fair correlation of max HR and physical effort. No relationships existed between [La]/HR and session-RPE. A unit increase in bout-RPE resulted in a 2.09 unit increase in physical, or a 1.36 unit increase in mental, effort holding all other bout variables constant. Gender and competitive level did not influence statistical models., CONCLUSIONS: Results provide further evidence that RPE can be used across a range of competitive levels and genders to monitor workload of mixed sessions and individual randori in judo. Physical effort may play a larger role than mental effort when athletes reflect on exertion during training. Copyright © 2018. Published by Elsevier Ltd.
Keywords: *Martial Arts/ph [Physiology]; *Physical Exertion; *Workload; Adolescent; Adult; Athletes; Athletic performance; Combat sport; Cross-Sectional Studies; Epidemiological monitoring; Female; Heart Rate; Humans; Judo; Lactic Acid; Lactic Acid/bl [Blood]; Male; Martial Arts; Martial arts; Physical Exertion; Training load; Workload; Young Adult; adolescent; adult; article; athlete; athletic performance; blood; comparative effectiveness; cross-sectional study; dept.hms; drug efficacy; epidemiological monitoring; exercise; female; gender; heart rate; human; human experiment; human tissue; judo; lactic acid; male; martial art; peer-reviewed; physiology; workload; young adult

Muscle strength assessment - Axtell, Robert S. (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Special considerations for the lifespan: Elderly population - Robertson, M.I.; Axtell, Robert (ACSM's Exercise Testing and Prescription, 2018)
ACSM’S Exercise Testing and Prescription adapts and expands upon the assessment and exercise prescription-related content from ACSM’s Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom resource. Fully aligned with the latest edition of ACSM’s flagship title, ACSM’s Guidelines for Exercise Testing and Prescription , this practical resource walks students through the process of selecting and administering fitness assessments, using Guidelines to interpret results, and drafting an exercise prescription that is in line with Guidelines parameters .Designed for today’s learners, the text is written in a clear, concise style, and enriched by visuals that promote student engagement. As an American College of Sports Medicine publication, the book offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.The nuances of fitness assessment and the particulars of crafting exercise prescriptions are explored in expansive sections throughout the book.A full section devoted to Special Populations prepares students to meet the needs of the full range of both typically healthy and special needs clients they’ll see in practice.Comprehensive case studies written by experts to reinforce practical applications of concepts.A wide range of online resources includes laboratory materials and activities that provide opportunities for hands-on learning, and a library of journal articles that helps students connect research to practice.100% alignment with the most up-to-date version of the ACSM’s Guidelines for Exercise Testing and Prescription enhances the learning experience, making it easy to go back and forth between Guidelines and the text.eBook available. Fast, smart, and convenient, today’s eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.
Keywords: dept.hms

Effect of age on dynamic walking balance in a healthy population between the ages of 20 and 80 years - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2018)
Keywords: dept.hms; peer-reviewed

Dose of physical activity, physical functioning and disability risk in mobility-limited older adults: Results from the LIFE study randomized trial. - Fielding, Roger A; Guralnik, Jack M; King, Abby C; Pahor, Marco; McDermott, Mary M; Tudor-Locke, Catrine; Manini, Todd M; Glynn, Nancy W; Marsh, Anthony P; Axtell, Robert S; Hsu, Fang-Chi; Rejeski, W Jack; et al. (PLoS ONE, 2017)
Understanding the minimal dose of physical activity required to achieve improvement in physical functioning and reductions in disability risk is necessary to inform public health recommendations. To examine the effect of physical activity dose on changes in physical functioning and the onset of major mobility disability in The Lifestyle Interventions and Independence for Elders (LIFE) Study. We conducted a multicenter single masked randomized controlled trial that enrolled participants in 2010 and 2011 and followed them for an average of 2.6 years. 1,635 sedentary men and women aged 70-89 years who had functional limitations were randomized to a structured moderate intensity walking, resistance, and flexibility physical activity program or a health education program. Physical activity dose was assessed by 7-day accelerometry and self-report at baseline and 24 months. Outcomes included the 400 m walk gait speed, the Short Physical Performance Battery (SPPB), assessed at baseline, 6, 12, and 24 months, and onset of major mobility disability (objectively defined by loss of ability to walk 400 m in 15 min). When the physical activity arm or the entire sample were stratified by change in physical activity from baseline to 24 months, there was a dose-dependent increase in the change in gait speed and SPPB from baseline at 6, 12, and 24 months. In addition, the magnitude of change in physical activity over 24 months was related to the reduction in the onset of major mobility disability (overall P < 0.001) (highest versus the lowest quartile of physical activity change HR 0.23 ((95% CI:0.10-0.52) P = 0.001) in the physical activity arm. We observed a dose-dependent effect of objectively monitored physical activity on physical functioning and onset of major mobility disability. Relatively small increases (> 48 minutes per week) in regular physical activity participation had significant and clinically meaningful effects on these outcomes., TRIAL REGISTRATION: ClinicalsTrials.gov NCT00116194.
Keywords: *Activities of Daily Living; *Disabled Persons; *Exercise; *Mobility Limitation; Activities of Daily Living; Aged; Aged, 80 and over; Article; Disabled Persons; Exercise; Female; Humans; Male; Mobility Limitation; accelerometry; aged; controlled study; daily life activity; dept.hms; disabled person; education program; exercise; exercise intensity; female; human; incidence; major clinical study; male; multicenter study; outcome assessment; peer-reviewed; physical activity; physical activity, capacity and performance; physical disability; physical functioning; physical mobility; physical performance; randomized controlled trial; resistance training; risk assessment; risk factor; sedentary lifestyle; self report; very elderly; walking difficulty; walking speed

Device-measured physical activity as a predictor of disability in mobility-limited older adults - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh-Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang-Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al. (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. DESIGN: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. SETTING: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long-term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility-limited older adults. PARTICIPANTS: LIFE Study participants (n = 1,590) had a mean age +/- standard deviation of 78.9 +/- 5.2, low levels of PA, and measured mobility-relevant functional impairment at baseline. MEASUREMENTS: Activity data were collected using hip-worn 7-day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (¿= 2 consecutive instances of MMD). RESULTS: At baseline, every 30 minutes spent being sedentary (¡100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry-based PA as a time-dependent variable. CONCLUSION: Accelerometry-based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.
Keywords: Accelerometry; Aged; Aged, 80 and over; Article; Disability Evaluation; Exercise; Female; Geriatric Assessment; Humans; Male; Mini Mental State Examination; Mobility Limitation; Physical Therapy Modalities; Pittsburgh Sleep Quality Index; Sedentary Lifestyle; Time Factors; accelerometry; aged; clinical trial; cohort analysis; controlled study; depression; dept.hms; disability; educational status; ethnic group; exercise; female; functional disease; geriatric assessment; health education; human; major clinical study; major mobility disability; male; marriage; mobility disability; multicenter study; older adults; peer-reviewed; persistent major mobility disability; physical activity; physiotherapy; procedures; prospective study; randomized controlled trial; sedentary lifestyle; sedentary time; sleep quality; time factor; very elderly; walking difficulty

Effects of a Long-Term Physical Activity Program on Activity Patterns in Older Adults. - Wanigatunga, Amal A; Tudor-Locke, Catrine; Axtell, Robert S; Glynn, Nancy W; King, Abby C; McDermott, Mary M; Fielding, Roger A; Lu, Xiaomin; Pahor, Marco; Manini, Todd M (Medicine and science in sports and exercise, 2017)
PURPOSE: To examine the effect of a long-term structured physical activity (PA) intervention on accelerometer-derived metrics of activity pattern changes in mobility-impaired older adults., METHODS: Participants were randomized to either a PA or health education (HE) program. The PA intervention included a walking regimen with strength, flexibility, and balance training. The HE program featured health-related discussions and a brief upper body stretching routine. Participants (n = 1341) wore a hip-worn accelerometer for >=10 h.d for >=3 d at baseline and again at 6, 12, and 24 months postrandomization. Total PA (TPA)-defined as movements registering 100+ counts per minute-was segmented into the following intensities: low-light PA (LLPA; 100-759 counts per minute), high light PA (HLPA; 760-1040 counts per minute), low moderate PA (LMPA; 1041-2019 counts per minute), and high moderate and greater PA (HMPA; 2020+ counts per minute). Patterns of activity were characterized as bouts (defined as the consecutive minutes within an intensity)., RESULTS: Across groups, TPA decreased an average of 74 min.wk annually. The PA intervention attenuated this effect (PA = -68 vs HE: -112 min.wk, P = 0.002). This attenuation shifted TPA composition by increasing time in LLPA (10+ bouts increased 6 min.wk), HLPA (1+, 2+, 5+, and 10+ bouts increased 6, 3, 2, and 1 min.wk, respectively), LMPA (1+, 2+, 5+, and 10+ bouts increased: 19, 17,16, and 8 min.wk, respectively), and HMPA (1+, 2+, 5+, and 10+ bouts increased 23, 21, 17, and 14 min.wk, respectively)., CONCLUSIONS: The PA intervention increased PA by shifting the composition of activity toward higher-intensity activity in longer-duration bouts. However, a long-term structured PA intervention did not completely eliminate overall declines in total daily activity experienced by mobility-impaired older adults.
Keywords: *Aged/ph [Physiology]; *Exercise; *Health Promotion; ACCELEROMETER; ACTIVITY BOUTS; Accelerometry; Age Factors; Aged; Aged, 80 and over; ELDERLY; Exercise; Female; Health Promotion; Humans; LIGHT-INTENSITY PHYSICAL ACTIVITY; Male; Mobility Limitation; PHYSICAL ACTIVITY INTERVENTION; Program Evaluation; Sedentary Behavior; Sedentary Lifestyle; accelerometry; age; aged; clinical trial; controlled study; dept.hms; exercise; female; health promotion; human; male; multicenter study; peer-reviewed; physiology; program evaluation; randomized controlled trial; sedentary lifestyle; very elderly; walking difficulty

Household support for physical activity in adolescent girls recruited from lower SES neighborhoods - Rupp, Kristie; Taverno Ross, Sharon E.; Gary-Webb, Tiffany L.; Akiva, Thomas; Jakicic, John M. (Medicine & Science in Sports & Exercise, 2017)
Keywords: dept.hms

Guideposts and roadblocks to the career-long scholarly engagement of physical education teacher education faculty - Berei, Catherine P; Pratt, Erica; Parker, Melissa; Shephard, Kevin; Liang, Tanjian; Nampai, Udon; Neamphoka, Guntima (Research Quarterly for Exercise and Sport, 2017)
Purpose: Scholarship is essential for the growth and development of the physical education field. Over time, scholarship expectations have changed, forcing faculty members to alter time spent for research, teaching, and service. Social-cognitive career theory (SCCT) presents a model for understanding performance and persistence in an occupational environment. The interconnected aspects of SCCT have different emphasis related to self-efficacy, outcome expectations, or personal goals pursuit. This study explored physical education teacher education (PETE) faculty members' continuing engagement in scholarly activity through SCCT. Method: Data collection included interviews with 9 senior PETE faculty members who met the criteria for “productive scholars over time.” Curriculum vitae were collected to verify productivity. Results: Data analysis revealed guidepost themes that included collaborating, finding balance, defining a research process, and maintaining a strong work ethic. Roadblocks encountered included other obligations and lack of support for research. Conclusions: Participants demonstrated strong self-efficacy; held high, positive expectations for success; and set very specific, clear, and deliberate goals. Participant behavior was moderated by their personal attributes (capacity to build relationships, set goals, and maintain interest and passion) and was tempered by the environments in which they worked. Fostering similar behaviors has the potential to guide future and current PETE faculty members in creating supportive and encouraging atmospheres for sustained productivity. The lack of literature relating to this topic warrants the need for more research exploring the influential factors and benefits gained from sustained scholarly productivity over time for PETE faculty members.
Keywords: Academic publishing; Ethics, Professional; Female; Goals; Humans; Male; Physical Education and Training; Research; School Teachers; Self Efficacy; adult; atmosphere; barriers to productivity; career; curriculum; data analysis; dept.hms; expectation; faculty research productivity; female; higher education research; human; human experiment; interview; male; medical ethics; motivation; peer-reviewed; physical education; productivity; psychology; publishing; research; school teacher; self concept; teacher training; theoretical study

Concurrent validation of the tandem walk test as a measure of dynamic walking balance in a healthy population - Robertson, Marc; Gregory, Robert (Physical Therapy and Rehabilitation, 2017)
Keywords: dept.hms; peer-reviewed